Electrostatic image developer, process cartridge, image forming apparatus and image forming method

The electrostatic image developer with specific toner and carrier properties effectively suppresses fogging by ensuring proper charging and distribution of additives, addressing the issue of toner aggregation in existing developers.

JP7613260B2Active Publication Date: 2025-01-15FUJIFILM BUSINESS INNOVATION CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021085620
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-20
Publication Date
2025-01-15
Estimated Expiration
2041-05-20

AI Technical Summary

Technical Problem

Existing electrostatic image developers experience fogging due to insufficient toner charging and aggregation, which is not effectively addressed by current technologies.

Method used

The development of an electrostatic image developer with toner particles having a surface property index value of 1.0 to 2.0 and a carrier with a ratio B/A of 1.020 to 1.100, incorporating a resin layer with controlled thickness and inorganic particles, ensuring adequate triboelectric charging and reduced aggregation.

Benefits of technology

The solution significantly reduces fogging by ensuring uniform distribution of external additives, maintaining sufficient toner charge, and preventing aggregation, thereby improving image quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007613260000004
    Figure 0007613260000004
  • Figure 0007613260000005
    Figure 0007613260000005
  • Figure 0007613260000001
    Figure 0007613260000001
Patent Text Reader

Abstract

To provide an electrostatic charge image developer which suppresses occurrence of fogging.SOLUTION: An electrostatic charge image developer has: a toner which contains toner particles and an external additive, and has a toner having a surface property index value of the toner particles of 1.0 or more and less than 2.0; and a carrier which has magnetic particles and a resin layer coating the magnetic particles, and has a ratio B / A of a surface area B to a planar view area A when the surface is three-dimensionally analyzed of 1.020 or more and 1.100 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an electrostatic image developer, a process cartridge, an image forming apparatus, and an image forming method. [Background technology]

[0002] Patent Document 1 discloses a toner for developing electrostatic images having a surface property index value of 2.0 or more and 2.8 or less. Patent Document 2 discloses a carrier for developing electrostatic images, which includes a carrier body having a core material and a coating resin layer, and spherical silica particles having a volume average particle size of 50 nm or more and 300 nm or less and adhering to the surface of the carrier body in a ratio of 0.001 part by mass or more and 0.100 part by mass or less per 10 parts by mass of the carrier body. Patent Document 3 discloses an electrostatic image developer containing a carrier having a resin coating layer on a core material and a toner, the carrier containing 7 to 35 mass % of silica or carbon black in the resin coating layer, the coating resin having a weight average molecular weight of 300,000 to 600,000, and the toner containing external additive fine particles having a number average particle diameter of 70 to 300 nm. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2019-168533 A [Patent Document 2] JP 2011-186005 A [Patent Document 3] JP 2008-304745 A Summary of the Invention [Problem to be solved by the invention]

[0004] The present disclosure has an object to provide an electrostatic image developer comprising a toner containing toner particles and an external additive, and a carrier having magnetic particles and a resin layer, which suppresses the occurrence of fogging compared to an electrostatic image developer in which the toner particles have a surface index value of 2.0 or more, or an electrostatic image developer in which, when the carrier surface is three-dimensionally analyzed, the ratio B / A of the planar area A to the surface area B is less than 1.020 or exceeds 1.100. [Means for solving the problem]

[0005] Means for solving the above problems include the following aspects.

[0006] <1> a toner comprising toner particles and an external additive, the toner particles having a surface property index value of 1.0 or more and less than 2.0; a carrier having magnetic particles and a resin layer covering the magnetic particles, the ratio B / A of a planar area A to a surface area B being 1.020 or more and 1.100 or less when the surface is three-dimensionally analyzed; 1. An electrostatic image developer comprising: <2> The surface property index value is 1.2 or more and 1.8 or less. <1> Electrostatic image developer according to claim 1. <3> The ratio B / A is 1.040 or more and 1.080 or less. <1> or <2> Electrostatic image developer according to claim 1. <4> The resin layer contains inorganic particles, and the average particle size of the inorganic particles is 5 nm or more and 90 nm or less. <1> ~ <3> 2. The electrostatic image developer according to claim 1 . <5> The average particle size of the inorganic particles is 5 nm or more and 70 nm or less. <4> Electrostatic image developer according to claim 1. <6> The average thickness of the resin layer is 0.6 μm or more and 1.4 μm or less. <1> ~ <5> 2. The electrostatic image developer according to claim 1 . <7> The average thickness of the resin layer is 0.8 μm or more and 1.2 μm or less. <6> Electrostatic image developer according to claim 1. <8> The toner has a storage modulus G' of 6.0×10 at a temperature of 30° C. in dynamic viscoelasticity measurement. 8 Pa or more 1.5×10 9Pa or less, <1> ~ <7> 2. The electrostatic image developer according to claim 1 . <9> The storage elastic modulus G' is 8.0×10 8 Pa or more 1.2×10 9 Pa or less, <8> Electrostatic image developer according to claim 1. <10> the resin layer contains silica particles, The silicon element concentration on the surface of the carrier measured by X-ray photoelectron spectroscopy is more than 2 atomic% and less than 20 atomic%. <1> ~ <9> 2. The electrostatic image developer according to claim 1 . <11> The weight average molecular weight of the resin contained in the resin layer is less than 300,000; <1> ~ <10> 2. The electrostatic image developer according to claim 1 . <12> <1> ~ <11> and a developing unit that contains the electrostatic image developer according to any one of claims 1 to 5 and develops an electrostatic image formed on a surface of an image carrier into a toner image by the electrostatic image developer, A process cartridge that is detachably attached to an image forming apparatus. <13> An image carrier; a charging means for charging the surface of the image carrier; an electrostatic image forming means for forming an electrostatic image on the charged surface of the image carrier; <1> ~ <11> a developing unit that contains the electrostatic image developer according to any one of claims 1 to 5 and develops the electrostatic image formed on the surface of the image carrier into a toner image by the electrostatic image developer; a transfer means for transferring the toner image formed on the surface of the image carrier to a surface of a recording medium; a fixing means for fixing the toner image transferred onto the surface of the recording medium; An image forming apparatus comprising: <14> a charging step of charging the surface of the image carrier; an electrostatic image forming step of forming an electrostatic image on the charged surface of the image carrier; <1> ~ <11> a developing step of developing the electrostatic image formed on the surface of the image carrier into a toner image by using the electrostatic image developer according to any one of the above items; a transfer step of transferring the toner image formed on the surface of the image carrier onto a surface of a recording medium; a fixing step of fixing the toner image transferred onto the surface of the recording medium; The image forming method according to claim 1, Effect of the Invention

[0007] <1> According to the invention, there is provided an electrostatic image developer which suppresses the occurrence of fogging compared to an electrostatic image developer in which the surface property index value of the toner particles is 2.0 or more, or an electrostatic image developer in which the ratio B / A of the planar area A to the surface area B when the carrier surface is three-dimensionally analyzed is less than 1.020 or exceeds 1.100. <2> According to the invention, there is provided an electrostatic image developer which suppresses the occurrence of fogging, as compared with an electrostatic image developer in which the surface index value of the toner particles is less than 2.2 or exceeds 2.6. <3> According to the present invention, there is provided an electrostatic image developer which suppresses the occurrence of fogging, as compared with an electrostatic image developer in which the ratio B / A of the planar area A to the surface area B is less than 1.040 or exceeds 1.080 when the carrier surface is three-dimensionally analyzed. <4> According to the present invention, an electrostatic image developer is provided which is less susceptible to fogging than an electrostatic image developer in which the average particle size of the inorganic particles contained in the resin layer of the carrier is less than 5 nm or exceeds 90 nm. <5> According to the present invention, an electrostatic image developer is provided which is less susceptible to fogging than an electrostatic image developer in which the average particle size of the inorganic particles contained in the resin layer of the carrier is less than 5 nm or exceeds 70 nm. <6> According to the present invention, there is provided an electrostatic image developer which is less susceptible to fogging than an electrostatic image developer in which the average thickness of the resin layer of the carrier is less than 0.6 μm or exceeds 1.4 μm. <7> According to the present invention, there is provided an electrostatic image developer which is less susceptible to fogging than an electrostatic image developer in which the average thickness of the resin layer of the carrier is less than 0.8 μm or exceeds 1.2 μm. <8> According to the invention, the storage modulus G' of the toner is 6.0×10 8 Less than Pa or 1.5×10 9As a result, an electrostatic image developer that suppresses the occurrence of fogging compared to an electrostatic image developer having a surface area of ​​10 Pa or more is provided. <9> According to the invention, the storage modulus G' of the toner is 8.0×10 8 Less than Pa or 1.2×10 9 As a result, an electrostatic image developer that suppresses the occurrence of fogging compared to an electrostatic image developer having a surface area of ​​10 Pa or more is provided. <10> According to the present invention, an electrostatic image developer is provided which is less susceptible to fogging than an electrostatic image developer in which the silicon concentration on the carrier surface is 2 atomic % or less or 20 atomic % or more. <11> According to the present invention, an electrostatic image developer is provided which is less susceptible to fogging than an electrostatic image developer in which the weight average molecular weight of the resin contained in the resin layer of the carrier is 300,000 or more. <12> According to the invention, a process cartridge is provided which suppresses the occurrence of fogging compared to a process cartridge containing an electrostatic image developer whose toner particles have a surface property index value of 2.0 or more, or an electrostatic image developer whose carrier surface is analyzed in three dimensions and in which the ratio B / A of the planar area A to the surface area B is less than 1.020 or exceeds 1.100. <13> According to the invention, there is provided an image forming apparatus which suppresses the occurrence of fogging, compared to an image forming apparatus which contains an electrostatic image developer in which the toner particles have a surface property index value of 2.0 or more, or an electrostatic image developer in which the ratio B / A of the planar area A to the surface area B when the carrier surface is analyzed in three dimensions is less than 1.020 or exceeds 1.100. <14> According to the invention, there is provided an image forming method which suppresses the occurrence of fogging, compared to an image forming method which uses an electrostatic image developer in which the surface property index value of the toner particles is 2.0 or more, or an electrostatic image developer in which the ratio B / A of the planar area A to the surface area B when the carrier surface is three-dimensionally analyzed is less than 1.020 or exceeds 1.100. [Brief description of the drawings]

[0008] [Figure 1] 1 is a schematic configuration diagram illustrating an example of an image forming apparatus according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram illustrating an example of a process cartridge that is detachably mounted to the image forming apparatus according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, embodiments of the present disclosure will be described. These descriptions and examples are merely illustrative of the embodiments, and are not intended to limit the scope of the embodiments.

[0010] In the present disclosure, a numerical range indicated using "~" indicates a range that includes the numerical values ​​before and after "~" as the minimum and maximum values, respectively.

[0011] In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples.

[0012] In the present disclosure, the term "step" includes not only an independent step, but also a step that cannot be clearly distinguished from other steps, as long as the intended purpose of the step is achieved.

[0013] When an embodiment of the present disclosure is described with reference to the drawings, the configuration of the embodiment is not limited to the configuration shown in the drawings. In addition, the size of the members in each drawing is conceptual, and the relative relationship between the sizes of the members is not limited to this.

[0014] In the present disclosure, each component may contain multiple types of corresponding substances. When referring to the amount of each component in a composition in the present disclosure, if multiple substances corresponding to each component are present in the composition, the total amount of the multiple substances present in the composition is meant unless otherwise specified.

[0015] In the present disclosure, the particles corresponding to each component may include multiple types. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component means the value for a mixture of the multiple types of particles present in the composition, unless otherwise specified.

[0016] In the present disclosure, "(meth)acrylic" means at least one of acrylic and methacrylic, and "(meth)acrylate" means at least one of acrylate and methacrylate.

[0017] In this disclosure, "toner for developing electrostatic images" is also referred to as "toner", "carrier for developing electrostatic images" is also referred to as "carrier", and "electrostatic image developer" is also referred to as "developer".

[0018] <Electrostatic image developer> The developer according to this embodiment is a two-component developer containing a toner and a carrier. In this embodiment, the mixing ratio (mass ratio) of the toner and the carrier is preferably toner:carrier=1:100 to 30:100, more preferably 3:100 to 20:100, and further preferably 5:100 to 15:100.

[0019] The toner in the present embodiment contains toner particles and an external additive, and the surface property index value of the toner particles is 1.0 or more and less than 2.0. In this embodiment, the surface property index value of the toner particles is an index for evaluating the unevenness of the toner particle surface. The closer the surface property index value is to 1.0, the smoother the toner particle surface tends to be, and the farther the surface property index value is from 1.0, the rougher the toner particle surface tends to be. The surface property index value of the toner particles is calculated from the following formulas 1 and 2.

[0020] Formula 1: Surface property index value of toner particles = measured specific surface area of ​​toner particles / calculated specific surface area of ​​toner particles Equation 2: Calculated specific surface area of ​​toner particles = sum of surface areas calculated from the circle-equivalent diameters of 4,500 toner particles in flow particle image analysis / (density of toner particles x sum of volumes calculated from the circle-equivalent diameters of 4,500 toner particles in flow particle image analysis)

[0021] The measured value of the specific surface area of ​​the toner particles is determined from the amount of nitrogen adsorption by the BET one-point method (equilibrium relative pressure 0.3). A flow type particle image analyzer, FPIA-3000 manufactured by Sysmex Corporation, is used for the flow type particle image analysis performed to obtain the calculated value of the specific surface area of ​​the toner particles. The FPIA-3000 captures the image of the toner particles, processes the two-dimensional image, and calculates the equivalent circle diameter from the projected area. Assuming that the toner particles are perfect spheres, the surface area and volume of the perfect sphere are calculated from the equivalent circle diameter. The sum of the surface areas and the sum of the volumes are calculated from the equivalent circle diameters of 4,500 toner particles. The density of the toner particles is measured by using a Gay-Lussac type pycnometer to measure the true density in accordance with 8.2.2 of JIS K0061:2001. The toner particles used for the measurement are toner particles from which external additives have been removed. The external additives are removed from the surface of the toner by repeatedly subjecting the toner to ultrasonic treatment in water containing a surfactant and washing with water.

[0022] The carrier in this embodiment is a resin-coated carrier having magnetic particles and a resin layer that coats the magnetic particles. In this embodiment, the ratio B / A of the planar area A to the surface area B is 1.020 or more and 1.100 or less when the surface is analyzed three-dimensionally. In this embodiment, the ratio B / A is an index for evaluating the unevenness of the carrier surface, and is determined by the following method.

[0023] As a device for three-dimensionally analyzing the carrier surface, a scanning electron microscope having four secondary electron detectors (for example, ERA-8900FE, electron beam three-dimensional roughness analyzer manufactured by Elionix Co., Ltd.) is used, and the analysis is performed as follows. The surface of one carrier particle is magnified 5000 times. The measurement points are spaced 0.06 μm apart, 400 points are measured along the long side and 300 points along the short side, and an area of ​​24 μm x 18 μm is measured to obtain 3D image data. For the three-dimensional image data, the limit wavelength of a spline filter (a frequency-selective filter that uses a spline function) is set to 12 μm to remove wavelengths with a period of 12 μm or more, thereby removing the waviness components of the carrier surface, extracting the roughness components, and obtaining a roughness curve. Furthermore, the cutoff value of a Gaussian high-pass filter (a frequency-selective filter using a Gaussian function) is set to 2.0 μm to remove wavelengths with a period of 2.0 μm or more, thereby removing wavelengths corresponding to the convex parts of the magnetic particles exposed on the carrier surface from the roughness curve after spline filter processing, thereby obtaining a roughness curve from which wavelength components with a period of 2.0 μm or more have been removed. From the 3D roughness curve data after filtering, the central 12 μm × 12 μm area (planar area A = 144 μm 2 ) surface area B (μm 2 ) and calculate the ratio B / A. Calculate the ratio B / A for each of 100 carriers and take the arithmetic average.

[0024] The electrostatic image developer according to the present embodiment suppresses the occurrence of fogging. "Fogging" is a phenomenon in which toner scatters and unintended tiny dot-like images appear on the image forming surface of a recording medium. The following is presumed to be the mechanism by which the present embodiment suppresses the occurrence of fogging.

[0025] The toner is triboelectrically charged by being stirred together with the carrier in the developing device. If the toner is not sufficiently charged, the toner will not adhere to the image carrier during development and will scatter, resulting in fogging. One of the measures to prevent fogging is to prevent toner aggregation in the developing device, thoroughly stir each toner, and sufficiently triboelectrically charge each toner.

[0026] The developer of this embodiment has a surface property index value of less than 2.0 for the toner particles, and a carrier surface ratio B / A of 1.020 or more. That is, the developer of this embodiment has a relatively small height difference between the unevenness of the toner particle surface, and the number of unevennesses on the carrier surface is relatively large, or the height difference between the unevenness of the carrier surface is relatively large. It is presumed that the developer of this embodiment having such surface characteristics has a small bias in the distribution of the external additive on the toner particle surface when stirred in a developing device, and the external additive easily moves between the toner particle surface and the protruding parts of the carrier surface. As a result, a sufficient amount of the external additive is distributed on the toner particle surface with little bias, so that it is presumed that toner aggregation is unlikely to occur in the developing device, and the individual toner particles are well stirred. It is presumed that if the surface property index value of the toner particles is 2.0 or more, the difference in height between the concaves and convexities of the toner particle surface is too large, so that the external additives tend to be concentrated in the concaves of the toner particle surface, resulting in less external additives on the convex parts of the toner particle surface.Then, the toner aggregates via the convex parts of the toner particle surface where the external additives are scarce, and the individual toner particles are not thoroughly stirred, resulting in toner with an insufficient amount of charge, and causing fogging. If the ratio B / A of the carrier surface is less than 1.020, the carrier surface is too flat, and the contact area between the toner and the carrier becomes large, which is believed to result in a large amount of external additives transferring from the toner to the carrier. As a result, the toner with less external additives aggregates, and the individual toner particles are not thoroughly stirred, resulting in toner with an insufficient charge, which is believed to cause fogging. On the other hand, if the ratio B / A of the carrier surface exceeds 1.100, the number of irregularities on the carrier surface is too large or the difference in height between the irregularities on the carrier surface is too large, so that the amount of external additives entering the recesses on the carrier surface increases, and the amount of external additives returning from the carrier to the toner decreases. Then, the toner with less external additives aggregates, and the individual toner particles are not thoroughly stirred, resulting in toner with an insufficient amount of charge, which is presumed to cause fogging. From the viewpoint of suppressing the above phenomenon, in the developer of this embodiment, the surface property index value of the toner particles is less than 2.0, and the ratio B / A of the carrier surface is 1.020 or more and 1.100 or less.

[0027] For the above reasons, the ratio B / A on the carrier surface is preferably 1.030 or more and 1.090 or less, more preferably 1.040 or more and 1.080 or less, and even more preferably 1.040 or more and 1.070 or less. For the above reasons, the surface index value of the toner particles is preferably 1.9 or less, more preferably 1.8 or less, and even more preferably 1.7 or less. Since it is difficult to produce toner particles having a surface index value of less than 1.0, from the viewpoint of ease of production, the surface index value of the toner particles is 1.0 or more, preferably 1.1 or more, more preferably 1.2 or more, and even more preferably 1.3 or more.

[0028] When the toner particles are produced by an aggregation-coalescence method, the surface property index value of the toner particles can be controlled by adjusting the temperature or pH when fusing and coalescing aggregated particles containing resin particles. The ratio B / A on the carrier surface can be controlled by the manufacturing conditions for forming the resin layer, as will be described in detail later.

[0029] The toner and carrier in this embodiment will be described in detail.

[0030] <Toner> The toner has a storage modulus G' of 6.0 x 10 at 30°C in dynamic viscoelasticity measurement. 8 Pa or more 1.5×10 9 It is preferable that the pressure is 0.1 Pa or less. The storage modulus G' means the elastic response component of the elastic modulus in the relationship between the stress generated against the distortion when deforming, and the larger the value of the storage modulus G', the harder the toner tends to be. When a crystalline polyester resin is used, the temperature of 30° C. is a temperature at which phase separation between the amorphous polyester resin and the crystalline polyester resin is maintained, and in this embodiment, the temperature for evaluating the hardness of the toner is specified to be 30° C.

[0031] The storage modulus G' of the toner at 30°C is 6.0×10 8When the pressure is equal to or higher than Pa, the external additive is less likely to be embedded in the toner particles, and aggregation of the toner with less external additive can be suppressed. As a result, the individual toner particles are thoroughly mixed, and toner with an insufficient charge is less likely to be produced, making it less likely that fogging will occur. The storage modulus G' of the toner at 30°C is 1.5×10 9 When the pressure is less than or equal to Pa, the external additives are less likely to separate from the toner particles, and since the external additives are retained on the surface of the toner particles, aggregation of the toner with less external additives can be suppressed. As a result, the individual toner particles are thoroughly stirred, and toner with an insufficient charge is less likely to be produced, and fogging is less likely to occur. From the above viewpoint, the storage modulus G' of the toner at a temperature of 30°C is 7.0×10 8 Pa or more 1.4×10 9 Pa or less is more preferable, and 8.0×10 8 Pa or more 1.2×10 9 Pa or less is more preferable. The storage modulus G' of the toner can be controlled by the ratio of the amounts of the amorphous resin and the crystalline resin contained in the toner, and the greater the amount of the crystalline resin, the lower the storage modulus G' of the toner tends to be.

[0032] The storage modulus G' of the toner is determined by carrying out dynamic viscoelasticity measurement as described below. Sample: Using a press molding machine, 0.25 g of toner is tableted into a disk having a diameter of 8 mm and a thickness of 4 mm in an environment of 25°C ± 3°C. Measurement equipment: Rheometer ARES, TA Instruments Measurement jig: 8mm parallel plate Frequency: 1Hz Angular frequency: 6.28rad / sec Distortion: 0.03~20% (automatic control) Thermal history: The sample is attached to a parallel plate adjusted to a temperature of 130°C, cooled to 30°C at a rate of 1°C / min, held at 30°C for 30 minutes, and then measured at 30°C.

[0033] [Toner particles] The toner particles are configured to contain, for example, a binder resin, and, if necessary, a colorant, a release agent, and other additives.

[0034] -Binding resin- Examples of the binder resin include vinyl resins made of homopolymers of monomers such as styrenes (e.g., styrene, parachlorostyrene, α-methylstyrene, etc.), (meth)acrylic acid esters (e.g., methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, lauryl methacrylate, 2-ethylhexyl methacrylate, etc.), ethylenically unsaturated nitriles (e.g., acrylonitrile, methacrylonitrile, etc.), vinyl ethers (e.g., vinyl methyl ether, vinyl isobutyl ether, etc.), vinyl ketones (e.g., vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropenyl ketone, etc.), and olefins (e.g., ethylene, propylene, butadiene, etc.), or copolymers of two or more of these monomers. Examples of the binder resin include non-vinyl resins such as epoxy resins, polyester resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, and modified rosin, mixtures of these with the vinyl resins, and graft polymers obtained by polymerizing vinyl monomers in the coexistence of these. These binder resins may be used alone or in combination of two or more kinds.

[0035] The binder resin is preferably a polyester resin. The polyester resin may be, for example, a known amorphous polyester resin. The polyester resin may be used in combination with a crystalline polyester resin together with the amorphous polyester resin. However, the content of the crystalline polyester resin is preferably in the range of 2% by mass to 40% by mass (preferably 2% by mass to 20% by mass) based on the total binder resin.

[0036] The "crystallinity" of a resin refers to the presence of a clear endothermic peak rather than a stepwise change in the amount of endothermic heat in differential scanning calorimetry (DSC); specifically, it refers to the half-width of the endothermic peak being within 10°C when measured at a heating rate of 10 (°C / min). On the other hand, the term "amorphous" for a resin refers to a half-width exceeding 10° C., a stepwise change in endothermic heat quantity, or no clear endothermic peak being observed.

[0037] Amorphous polyester resin The amorphous polyester resin may be, for example, a condensation polymer of a polyvalent carboxylic acid and a polyhydric alcohol. As the amorphous polyester resin, a commercially available product or a synthesized product may be used.

[0038] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenylsuccinic acid, adipic acid, sebacic acid, etc.), alicyclic dicarboxylic acids (e.g., cyclohexanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, naphthalenedicarboxylic acid, etc.), anhydrides thereof, and lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). Among these, aromatic dicarboxylic acids are preferable as polyvalent carboxylic acids. As the polyvalent carboxylic acid, a trivalent or higher carboxylic acid having a crosslinked or branched structure may be used in combination with a dicarboxylic acid. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, anhydrides thereof, and lower (e.g., carbon number 1 to 5) alkyl esters thereof. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.

[0039] Examples of polyhydric alcohols include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, etc.), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, hydrogenated bisphenol A, etc.), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among these, examples of polyhydric alcohols include aromatic diols and alicyclic diols, and more preferably aromatic diols. As the polyhydric alcohol, a polyhydric alcohol having a crosslinked or branched structure of three or more may be used in combination with the diol. Examples of the polyhydric alcohol having a trihydric or higher valence include glycerin, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.

[0040] The glass transition temperature (Tg) of the amorphous polyester resin is preferably 50°C or higher and 80°C or lower, and more preferably 50°C or higher and 65°C or lower. The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), and more specifically, it is determined from the "extrapolated glass transition onset temperature" described in the method for determining glass transition temperature in JIS K7121:1987 "Method for measuring transition temperature of plastics."

[0041] The weight average molecular weight (Mw) of the amorphous polyester resin is preferably 5,000 or more and 1,000,000 or less, and more preferably 7,000 or more and 500,000 or less. The number average molecular weight (Mn) of the amorphous polyester resin is preferably 2,000 or more and 100,000 or less. The molecular weight distribution Mw / Mn of the amorphous polyester resin is preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less. The weight average molecular weight and number average molecular weight are measured by gel permeation chromatography (GPC). The molecular weight measurement by GPC is performed using a Tosoh GPC HLC-8120GPC as the measuring device, a Tosoh TSKgel SuperHM-M (15 cm) column, and THF solvent. The weight average molecular weight and number average molecular weight are calculated from the measurement results using a molecular weight calibration curve created with a monodisperse polystyrene standard sample.

[0042] The amorphous polyester resin can be obtained by a known production method, for example, by carrying out the reaction while removing water and alcohol generated during condensation by setting the polymerization temperature to 180° C. or higher and 230° C. or lower, and reducing the pressure in the reaction system as necessary. If the raw material monomer is not soluble or compatible at the reaction temperature, a high boiling point solvent may be added as a solubilizing agent to dissolve it. In this case, the polycondensation reaction is carried out while distilling off the solubilizing agent. If a monomer with poor compatibility is present in the copolymerization reaction, it is recommended that the monomer with poor compatibility is condensed in advance with the acid or alcohol to be polycondensed, and then polycondensed with the main component.

[0043] Crystalline polyester resin The crystalline polyester resin may be, for example, a polycondensate of a polyvalent carboxylic acid and a polyhydric alcohol. As the crystalline polyester resin, a commercially available product or a synthesized product may be used. Here, the crystalline polyester resin is preferably a polycondensate using a straight-chain aliphatic polymerizable monomer rather than a polymerizable monomer having an aromatic ring, since it easily forms a crystalline structure.

[0044] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, etc.), anhydrides thereof, and lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent carboxylic acid include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrides, and their lower alkyl esters (e.g., carbon number 1 to 5). As the polyvalent carboxylic acid, a dicarboxylic acid having a sulfonic acid group and a dicarboxylic acid having an ethylenic double bond may be used in combination with these dicarboxylic acids. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.

[0045] Examples of polyhydric alcohols include aliphatic diols (for example, straight-chain aliphatic diols having 7 to 20 carbon atoms in the main chain). Examples of aliphatic diols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-eicosanedecanediol. Among these, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol are preferred as aliphatic diols. The polyhydric alcohol may be a trihydric or higher alcohol having a crosslinked or branched structure in combination with the diol. Examples of the trihydric or higher alcohol include glycerin, trimethylolethane, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.

[0046] Here, the polyhydric alcohol has an aliphatic diol content of 80 mol % or more, preferably 90 mol % or more.

[0047] The melting temperature of the crystalline polyester resin is preferably 50°C or higher and 100°C or lower, more preferably 55°C or higher and 90°C or lower, and even more preferably 60°C or higher and 85°C or lower. The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "peak melting temperature" described in the method for determining melting temperature in JIS K7121:1987 "Method for measuring transition temperature of plastics."

[0048] The weight average molecular weight (Mw) of the crystalline polyester resin is preferably 6,000 or more and 35,000 or less.

[0049] The crystalline polyester resin can be obtained, for example, by a known production method, like the amorphous polyester.

[0050] The content of the binder resin is preferably from 40% by mass to 95% by mass, more preferably from 50% by mass to 90% by mass, and even more preferably from 60% by mass to 85% by mass, based on the total mass of the toner particles.

[0051] -Coloring agent- Examples of colorants include carbon black, chrome yellow, Hansa Yellow, benzidine yellow, threne yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, Balkan orange, watch young red, permanent red, brilliant carmine 3B, brilliant carmine 6B, DuPont oil red, pyrazolone red, lithol red, rhodamine B lake, lake red C, pigment red, rose bengal, aniline blue, Examples of the dyes include pigments such as ultramarine blue, chalcoil blue, methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, and malachite green oxalate; and dyes such as acridine-based, xanthene-based, azo-based, benzoquinone-based, azine-based, anthraquinone-based, thioindigo-based, dioxazine-based, thiazine-based, azomethine-based, indigo-based, phthalocyanine-based, aniline black-based, polymethine-based, triphenylmethane-based, diphenylmethane-based, and thiazole-based dyes. The colorant may be used alone or in combination of two or more kinds.

[0052] The colorant may be surface-treated as necessary, or may be used in combination with a dispersant. In addition, a plurality of types of colorants may be used in combination.

[0053] The content of the colorant is preferably from 1% by mass to 30% by mass, and more preferably from 3% by mass to 15% by mass, based on the total mass of the toner particles.

[0054] -Release agent- Examples of the release agent include hydrocarbon waxes, natural waxes such as carnauba wax, rice wax, and candelilla wax, synthetic or mineral / petroleum waxes such as montan wax, and ester waxes such as fatty acid esters and montan acid esters. The release agent is not limited to these.

[0055] The melting temperature of the release agent is preferably 50°C or higher and 110°C or lower, and more preferably 60°C or higher and 100°C or lower. The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "peak melting temperature" described in the method for determining melting temperature in JIS K7121:1987 "Method for measuring transition temperature of plastics."

[0056] The content of the release agent is preferably from 1% by mass to 20% by mass, and more preferably from 5% by mass to 15% by mass, based on the total mass of the toner particles.

[0057] -Other additives- Examples of other additives include known additives such as magnetic materials, charge control agents, inorganic powders, etc. These additives are contained in the toner particles as internal additives.

[0058] -Characteristics of toner particles, etc.- The toner particles may be toner particles having a single layer structure, or may be toner particles having a so-called core-shell structure composed of a core portion (core particle) and a coating layer (shell layer) that coats the core portion. The toner particles having a core-shell structure may be composed of, for example, a core containing a binder resin and, if necessary, other additives such as a colorant and a release agent, and a coating layer containing the binder resin.

[0059] The volume average particle size (D50v) of the toner particles is preferably from 2 μm to 10 μm, and more preferably from 4 μm to 8 μm. The volume average particle size (D50v) of the toner particles is measured using a Coulter Multisizer II (manufactured by Beckman Coulter, Inc.), and the electrolyte is measured using an ISOTON-II (manufactured by Beckman Coulter, Inc.). For the measurement, 0.5 mg to 50 mg of the measurement sample is added to 2 ml of a 5 mass % aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate) as a dispersant, and this is then added to 100 ml to 150 ml of the electrolyte. The electrolyte with the sample suspended in it is dispersed for 1 minute using an ultrasonic disperser, and the particle size distribution of particles with diameters in the range of 2 μm to 60 μm is measured using a Coulter Multisizer II with an aperture diameter of 100 μm. The number of particles sampled is 50,000. The particle size distribution based on volume is plotted from the smallest diameter side, and the particle size at which the cumulative 50% is reached is defined as the volume average particle size D50v.

[0060] The average circularity of the toner particles is preferably 0.94 or more and 1.00 or less, and more preferably 0.95 or more and 0.98 or less. The average circularity of toner particles is calculated by (circular equivalent perimeter) / (perimeter) [(perimeter of a circle having the same projected area as the particle image) / (perimeter of the particle projected image)]. Specifically, it is a value measured by the following method. First, the toner particles to be measured are sucked and collected, flattened, and a still image of the particles is captured by instantaneous strobe light emission, and the particle image is analyzed by a flow-type particle image analyzer (FPIA-3000, manufactured by Sysmex Corporation). The number of samples to be taken in order to calculate the average circularity is 4,500. When the toner contains an external additive, the toner to be measured is dispersed in water containing a surfactant, and then ultrasonic treatment is performed to obtain toner particles from which the external additive has been removed.

[0061] [External additives] Examples of the external additive include inorganic particles. Examples of the inorganic particles include SiO2, TiO2, Al2O3, CuO, ZnO, SnO2, CeO2, Fe2O3, MgO, BaO, CaO, K2O, Na2O, ZrO2, CaO·SiO2, and K2O·(TiO2). n , Al2O3·2SiO2, CaCO3, MgCO3, BaSO4, MgSO4, etc.

[0062] The surface of the inorganic particles as an external additive may be subjected to a hydrophobic treatment. The hydrophobic treatment may be performed, for example, by immersing the inorganic particles in a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, and examples thereof include silane coupling agents, silicone oils, titanate coupling agents, and aluminum coupling agents. These may be used alone or in combination of two or more. The amount of the hydrophobizing agent is usually, for example, 1 part by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the inorganic particles.

[0063] Examples of external additives include resin particles (resin particles such as polystyrene, polymethyl methacrylate, and melamine resin), cleaning agents (for example, metal salts of higher fatty acids such as zinc stearate, and fluorine-based polymer particles), and the like.

[0064] The amount of the external additive is preferably from 0.01% by mass to 5% by mass, and more preferably from 0.01% by mass to 2.0% by mass, based on the toner particles.

[0065] [Toner manufacturing method] The toner can be obtained by producing toner particles and then externally adding an external additive to the toner particles.

[0066] The toner particles may be produced by any of a dry production method (e.g., a kneading and pulverizing method, etc.) and a wet production method (e.g., an aggregation and coalescence method, a suspension polymerization method, a dissolution suspension method, etc.). There is no particular limitation on these production methods, and any known production method may be used. Among these, it is preferable to obtain the toner particles by the aggregation and coalescence method.

[0067] Specifically, for example, when toner particles are produced by the aggregation and coalescence method, The toner particles are manufactured through a process including a step of preparing a resin particle dispersion in which resin particles to be a binder resin are dispersed (resin particle dispersion preparation step), a step of aggregating the resin particles (or other particles, if necessary) in the resin particle dispersion (in a dispersion after mixing other particle dispersions, if necessary) to form aggregated particles (aggregated particle formation step), and a step of heating the aggregated particle dispersion in which the aggregated particles are dispersed, fusing and coalescing the aggregated particles to form toner particles (fusion and coalescence step).

[0068] Each step will be described in detail below. In the following description, a method for obtaining toner particles containing a colorant and a release agent will be described, but the colorant and the release agent are used as necessary. Of course, additives other than the colorant and the release agent may be used.

[0069] -Resin particle dispersion preparation process- Along with a resin particle dispersion in which resin particles serving as a binder resin are dispersed, for example, a colorant particle dispersion in which colorant particles are dispersed, and a release agent particle dispersion in which release agent particles are dispersed are prepared.

[0070] The resin particle dispersion liquid is prepared, for example, by dispersing resin particles in a dispersion medium with the aid of a surfactant.

[0071] The dispersion medium used in the resin particle dispersion liquid is, for example, an aqueous medium. Examples of the aqueous medium include water such as distilled water and ion-exchanged water, alcohols, etc. These may be used alone or in combination of two or more kinds.

[0072] Examples of the surfactant include anionic surfactants such as sulfate salts, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyhydric alcohols. Among these, anionic surfactants and cationic surfactants are particularly preferred. The nonionic surfactants may be used in combination with anionic surfactants or cationic surfactants. The surfactant may be used alone or in combination of two or more kinds.

[0073] In the resin particle dispersion, the resin particles are dispersed in the dispersion medium by a general dispersion method such as a rotary shear type homogenizer, a ball mill having a media, a sand mill, or a dyno mill. Depending on the type of resin particles, the resin particles may be dispersed in the dispersion medium by a phase inversion emulsification method. The phase inversion emulsification method is a method in which the resin to be dispersed is dissolved in a hydrophobic organic solvent in which the resin is soluble, a base is added to the organic continuous phase (O phase) to neutralize it, and then an aqueous medium (W phase) is added to invert the phase from W / O to O / W, thereby dispersing the resin in the aqueous medium in the form of particles.

[0074] The volume average particle size of the resin particles dispersed in the resin particle dispersion is, for example, preferably from 0.01 μm to 1 μm, more preferably from 0.08 μm to 0.8 μm, and even more preferably from 0.1 μm to 0.6 μm. The volume average particle size of the resin particles is measured by using a particle size distribution obtained by measurement using a laser diffraction particle size distribution measuring device (for example, LA-700 manufactured by Horiba, Ltd.), subtracting the cumulative distribution from the small particle size side for the volume of the divided particle size range (channel), and measuring the particle size at which the cumulative distribution is 50% of all particles as the volume average particle size D50v. The volume average particle sizes of particles in other dispersions are measured in the same manner.

[0075] The content of the resin particles in the resin particle dispersion is preferably from 5% by mass to 50% by mass, and more preferably from 10% by mass to 40% by mass.

[0076] In the same manner as the resin particle dispersion liquid, for example, a colorant particle dispersion liquid and a release agent particle dispersion liquid are also prepared. That is, the volume average particle size, dispersion medium, dispersion method, and particle content of the particles in the resin particle dispersion liquid are the same for the colorant particles dispersed in the colorant particle dispersion liquid and the release agent particles dispersed in the release agent particle dispersion liquid.

[0077] -Agglomerated particle formation process- Next, the resin particle dispersion, the colorant particle dispersion, and the release agent particle dispersion are mixed together, and the resin particles, the colorant particles, and the release agent particles are hetero-aggregated in the mixed dispersion to form aggregated particles containing the resin particles, the colorant particles, and the release agent particles and having a diameter close to that of the target toner particles.

[0078] Specifically, for example, an aggregating agent is added to the mixed dispersion, the pH of the mixed dispersion is adjusted to be acidic (e.g., pH 2 or more and 5 or less), a dispersion stabilizer is added as necessary, and then the mixed dispersion is heated to a temperature close to the glass transition temperature of the resin particles (specifically, for example, glass transition temperature of the resin particles -30°C or more and glass transition temperature -10°C or less), and the particles dispersed in the mixed dispersion are aggregated to form aggregated particles. In the aggregated particle formation process, for example, the mixed dispersion may be stirred with a rotary shear homogenizer, an aggregating agent may be added at room temperature (e.g., 25°C), the pH of the mixed dispersion may be adjusted to an acidic state (e.g., pH 2 or more and 5 or less), a dispersion stabilizer may be added as necessary, and then the mixture may be heated.

[0079] Examples of the flocculant include a surfactant having a polarity opposite to that of the surfactant contained in the mixed dispersion, an inorganic metal salt, and a divalent or higher metal complex. When a metal complex is used as the flocculant, the amount of the surfactant used is reduced, and the charging characteristics are improved. If necessary, an additive that forms a complex or a similar bond with the metal ion of the flocculant may be used together with the flocculant. As this additive, a chelating agent is preferably used.

[0080] Examples of inorganic metal salts include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate; and inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide. The chelating agent may be a water-soluble chelating agent, for example, oxycarboxylic acid such as tartaric acid, citric acid, gluconic acid, etc., aminocarboxylic acid such as iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), ethylenediaminetetraacetic acid (EDTA), etc. The amount of the chelating agent added is preferably 0.01 parts by mass or more and 5.0 parts by mass or less, and more preferably 0.1 parts by mass or more and less than 3.0 parts by mass, based on 100 parts by mass of the resin particles.

[0081] -Fusion / coalescence process- Next, the aggregated particle dispersion liquid in which the aggregated particles are dispersed is heated, for example, to a temperature equal to or higher than the glass transition temperature of the resin particles (for example, a temperature 10° C. to 30° C. higher than the glass transition temperature of the resin particles) to fuse and coalesce the aggregated particles to form toner particles.

[0082] Through the above steps, toner particles are obtained. After obtaining the aggregated particle dispersion in which the aggregated particles are dispersed, the aggregated particle dispersion and the resin particle dispersion in which the resin particles are dispersed are further mixed together to aggregate the aggregated particles so that the resin particles are further attached to the surfaces of the aggregated particles, thereby forming second aggregated particles; and the second aggregated particle dispersion in which the second aggregated particles are dispersed is heated to fuse and coalesce the second aggregated particles, thereby forming toner particles having a core-shell structure.

[0083] After the fusion and coalescence process is completed, the toner particles formed in the solution are subjected to a known washing process, solid-liquid separation process, and drying process to obtain dried toner particles. From the viewpoint of chargeability, the washing process is preferably performed by sufficient substitution washing with ion-exchanged water. From the viewpoint of productivity, the solid-liquid separation process is preferably performed by suction filtration, pressure filtration, etc. From the viewpoint of productivity, the drying process is preferably performed by freeze drying, air flow drying, fluidized drying, vibration type fluidized drying, etc.

[0084] The toner is produced by adding an external additive to dry toner particles and mixing them. The mixing may be performed using, for example, a V blender, a Henschel mixer, a Loedige mixer, etc. Furthermore, if necessary, coarse particles may be removed from the toner using a vibrating sieve, an air sieve, etc.

[0085] <Career> The carrier in this embodiment has magnetic particles and a resin layer that covers the magnetic particles.

[0086] [Magnetic particles] The magnetic particles are not particularly limited, and known magnetic particles used as the core material of carriers are applied.Specific examples of the magnetic particles include magnetic metal particles such as iron, nickel, and cobalt; magnetic oxide particles such as ferrite and magnetite; resin-impregnated magnetic particles in which porous magnetic powder is impregnated with resin; magnetic powder-dispersed resin particles in which magnetic powder is dispersed and mixed in resin; and the like.In this embodiment, the magnetic particles are preferably ferrite particles.

[0087] The volume average particle size of the magnetic particles is preferably from 15 μm to 100 μm, more preferably from 20 μm to 80 μm, and even more preferably from 30 μm to 60 μm. The volume average particle size herein means a particle size D50v that is 50% cumulative from the small diameter side in a volume-based particle size distribution.

[0088] The arithmetic mean height Ra (JIS B0601:2001) of the roughness curve of the magnetic particles is preferably 0.1 μm or more and 1 μm or less, and more preferably 0.2 μm or more and 0.8 μm or less. The arithmetic mean height Ra of the roughness curve of a magnetic particle is determined by observing the magnetic particle at an appropriate magnification (for example, 1000x magnification) using a surface shape measuring device (for example, Keyence Corporation's "Ultra-Deep Color 3D Shape Measuring Microscope VK-9700"), obtaining a roughness curve at a cutoff value of 0.08 mm, and extracting a reference length of 10 μm from the roughness curve in the direction of the average line. The Ra of 100 magnetic particles is calculated as the arithmetic mean.

[0089] The magnetic force of the magnetic particles is preferably 50 emu / g or more, more preferably 60 emu / g or more, in terms of saturation magnetization in a magnetic field of 3000 oersteds. The saturation magnetization is measured using a vibrating sample magnetic measuring device VSMP10-15 (manufactured by Toei Kogyo Co., Ltd.). The measurement sample is packed in a cell with an inner diameter of 7 mm and a height of 5 mm and set in the device. The measurement is performed by applying a magnetic field and sweeping up to a maximum of 3000 oersteds. The applied magnetic field is then reduced, and a hysteresis curve is prepared on a recording paper. The saturation magnetization, residual magnetization, and retentivity are determined from the curve data.

[0090] The volume resistivity of the magnetic particles is 1×10 5 Ω cm or more 1×10 9 Ω cm or less is preferable, and 1×10 7 Ω cm or more 1×10 9 Ω·cm or less is more preferable. The volume resistivity (Ω·cm) of magnetic particles is measured as follows: 2 The object to be measured is placed flat on the surface of the circular jig on which the electrode plate is arranged, with a thickness of 1 mm to 3 mm, to form a layer. 2The layer is sandwiched between two electrode plates. In order to eliminate any gaps between the objects being measured, a 4 kg load is placed on the electrode plate placed on the layer, and then the thickness of the layer (cm) is measured. Both the top and bottom electrodes of the layer are connected to an electrometer and a high-voltage power supply generator. A high voltage is applied to both electrodes so that the electric field is 103.8 V / cm, and the current value (A) that flows at this time is read. The measurement environment is a temperature of 20°C and a relative humidity of 50%. The formula for calculating the volume resistivity (Ω·cm) of the object being measured is as shown below. R=E×20 / (I-I0) / L In the above formula, R is the volume resistivity (Ω cm) of the object to be measured, E is the applied voltage (V), I is the current value (A), I0 is the current value (A) at an applied voltage of 0 V, and L is the layer thickness (cm). The coefficient 20 is the area of ​​the electrode plate (cm 2 )

[0091] [Resin layer] Examples of resins that make up the resin layer include styrene-acrylic acid copolymers; polyolefin resins such as polyethylene and polypropylene; polyvinyl or polyvinylidene resins such as polystyrene, acrylic resin, polyacrylonitrile, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl carbazole, polyvinyl ether, and polyvinyl ketone; vinyl chloride-vinyl acetate copolymers; straight silicone resins or modified products thereof consisting of organosiloxane bonds; fluororesins such as polytetrafluoroethylene, polyvinyl fluoride, polyvinylidene fluoride, and polychlorotrifluoroethylene; polyesters; polyurethanes; polycarbonates; amino resins such as urea-formaldehyde resins; and epoxy resins.

[0092] The resin layer preferably contains an acrylic resin having an alicyclic ring. As a polymerization component of the acrylic resin having an alicyclic ring, a lower alkyl ester of (meth)acrylic acid (for example, an alkyl (meth)acrylate ester having 1 to 9 carbon atoms in the alkyl group) is preferable, and specific examples thereof include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. These monomers may be used alone or in combination of two or more. The acrylic resin having an alicyclic ring preferably contains cyclohexyl (meth)acrylate as a polymerization component. The content of the monomer unit derived from cyclohexyl (meth)acrylate contained in the acrylic resin having an alicyclic ring is preferably 75% by mass or more and 100% by mass or less, more preferably 85% by mass or more and 100% by mass or less, and even more preferably 95% by mass or more and 100% by mass or less, based on the total mass of the acrylic resin having an alicyclic ring.

[0093] The weight-average molecular weight of the resin contained in the resin layer is preferably less than 300,000. When the weight-average molecular weight of the resin contained in the resin layer is less than 300,000, the strength of the resin layer is higher than when the weight-average molecular weight of the resin is 300,000 or more, and the resin layer is less likely to peel off when image formation is repeated. As a result, it is presumed that the toner is stirred well in the developing device, the toner is sufficiently triboelectrically charged, and the occurrence of fogging is suppressed. From the viewpoint of increasing the strength of the resin layer and making the resin layer less likely to peel off, the weight average molecular weight of the resin contained in the resin layer is preferably 50,000 or more and less than 300,000, more preferably 100,000 or more and 250,000 or less, and even more preferably 100,000 or more and 200,000 or less. From the above viewpoints, the weight average molecular weight of the acrylic resin having an alicyclic ring contained in the resin layer is preferably 50,000 or more and less than 300,000, more preferably 100,000 or more and 250,000 or less, and even more preferably 100,000 or more and 200,000 or less. When the resin layer contains a plurality of types of resins, the weight average molecular weight of the resins contained in the resin layer is a weighted average obtained by weighting the weight average molecular weight of each resin by the content ratio (mass basis) of each resin.

[0094] The weight average molecular weight of the resin contained in the resin layer is measured by gel permeation chromatography (GPC). The molecular weight measurement by GPC uses a Tosoh GPC HLC-8120GPC as the measuring device, a Tosoh TSKgel SuperHM-M (15 cm) column, and tetrahydrofuran as the solvent. The weight average molecular weight is calculated from the measurement results using a molecular weight calibration curve created with a monodisperse polystyrene standard sample.

[0095] The resin layer preferably contains inorganic particles. In this embodiment, carbon black is not considered to be an inorganic particle in the resin layer of the carrier.

[0096] When inorganic particles are contained in the resin layer, a carrier surface is formed with a moderate amount of fine irregularities. Most of these irregularities are covered with resin, but some of the inorganic particles may be exposed. Unlike resin, the exposed inorganic particles are not charged by contact with the toner, so excessive charging of the carrier surface can be suppressed. In addition, when the resin layer of the carrier is worn down by repeated image formation, the irregularities are selectively worn down and some of the inorganic particles in the resin layer are newly exposed. By continuing to expose some of the inorganic particles to the carrier surface, the chargeability of the carrier surface decreases and the increase in toner charge is suppressed, and as a result, the transferability of the toner image is easily maintained.

[0097] Examples of inorganic particles contained in the resin layer include metal oxide particles such as silica, titanium oxide, zinc oxide, and tin oxide, metal compound particles such as barium sulfate, aluminum borate, and potassium titanate, and metal particles such as gold, silver, and copper. Among these, silica particles are preferred.

[0098] The surface of the inorganic particles may be subjected to hydrophobic treatment. Examples of the hydrophobic treatment agent include known organosilicon compounds having an alkyl group (e.g., methyl group, ethyl group, propyl group, butyl group, etc.), and specific examples include alkoxysilane compounds, siloxane compounds, and silazane compounds. Among these, the hydrophobic treatment agent is preferably a silazane compound, and hexamethyldisilazane is preferable. The hydrophobic treatment agent may be used alone or in combination of two or more kinds.

[0099] Examples of methods for hydrophobizing inorganic particles with a hydrophobizing agent include a method in which supercritical carbon dioxide is used to dissolve the hydrophobizing agent in supercritical carbon dioxide and adhere the hydrophobizing agent to the surfaces of the inorganic particles; a method in which a solution containing a hydrophobizing agent and a solvent that dissolves the hydrophobizing agent is applied (e.g., sprayed or coated) to the surfaces of inorganic particles in the atmosphere to adhere the hydrophobizing agent to the surfaces of the inorganic particles; and a method in which a solution containing a hydrophobizing agent and a solvent that dissolves the hydrophobizing agent is added to an inorganic particle dispersion in the atmosphere, the solution is maintained, and then the mixed solution of the inorganic particle dispersion and the solution is dried.

[0100] The average particle size of the inorganic particles contained in the resin layer is preferably 5 nm or more and 90 nm or less. When the average particle size of the inorganic particles in the resin layer is 5 nm or more, a filler effect that increases the strength of the resin layer is easily obtained, and the resin layer is less likely to peel off when image formation is repeated. When the average particle size of the inorganic particles in the resin layer is 90 nm or less, the inorganic particles are less likely to be detached from the convex parts of the resin layer, and the resin layer is less likely to peel off when image formation is repeated. In either case, it is presumed that as a result, the toner is well stirred in the developing device, the toner is sufficiently triboelectrically charged, and the occurrence of fogging is suppressed. From the above viewpoints, the average particle size of the inorganic particles in the resin layer is more preferably 5 nm or more and 70 nm or less, further preferably 5 nm or more and 50 nm or less, and further preferably 8 nm or more and 50 nm or less. The average particle size of the inorganic particles contained in the resin layer can be controlled by the size of the inorganic particles used to form the resin layer.

[0101] The average thickness of the resin layer is preferably 0.6 μm or more and 1.4 μm or less. When the average thickness of the resin layer is 0.6 μm or more, the resin layer is unlikely to peel off when image formation is repeated. When the average thickness of the resin layer is 1.4 μm or less, the toner external additive is unlikely to adhere to or be embedded in the resin layer after migrating to the resin layer, and the amount of the external additive migrating from the toner to the carrier is not excessive. In either case, it is presumed that the result is good agitation of the toner in the developing device, sufficient triboelectric charging of the toner, and suppression of the occurrence of fogging. From the above viewpoints, the average thickness of the resin layer is more preferably 0.8 μm or more and 1.2 μm or less, and further preferably 0.8 μm or more and 1.1 μm or less. The average thickness of the resin layer can be controlled by the amount of resin used to form the resin layer, and the greater the amount of resin relative to the amount of magnetic particles, the greater the average thickness of the resin layer.

[0102] In this embodiment, the average particle diameter of the inorganic particles contained in the resin layer and the average thickness of the resin layer are determined by the following method. The carrier is embedded in epoxy resin and cut with a microtome to prepare a carrier cross section. The SEM image of the carrier cross section taken with a scanning electron microscope (SEM) is imported into an image processing analyzer for image analysis. 100 inorganic particles (primary particles) in the resin layer are randomly selected, and the circle equivalent diameter (nm) of each is determined and the arithmetic average is taken, which is the average particle size (nm) of the inorganic particles. In addition, 10 locations per carrier particle are randomly selected to measure the resin layer thickness (μm), and then the 100 carriers are measured and all the values ​​are arithmetically averaged, which is the average resin layer thickness (μm).

[0103] It is preferable that the resin layer of the carrier contains silica particles, and the silicon element concentration on the carrier surface determined by X-ray photoelectron spectroscopy is more than 2 atomic % and less than 20 atomic %. A silicon element concentration of more than 2 atomic % means that silica particles are appropriately distributed on the surface of the resin layer, and therefore the chargeability of the carrier surface is appropriately reduced. A silicon element concentration of less than 20 atomic % means that the amount of silica particles distributed on the resin layer surface is not too large, and therefore the chargeability of the carrier surface is not excessively reduced. In either case, it is presumed that the toner is appropriately triboelectrically charged as a result, and the occurrence of fogging is suppressed. From the above viewpoints, the silicon element concentration is more preferably more than 5 atomic % and less than 20 atomic %, and further preferably more than 6 atomic % and less than 19 atomic %. The silicon element concentration on the carrier surface can be controlled by the amount of silica particles used to form the resin layer, and the greater the amount of silica particles relative to the amount of resin, the higher the silicon element concentration on the carrier surface.

[0104] The silicon element concentration (atomic %) on the carrier surface is determined from the peak intensity of each element by analyzing the carrier as a sample by X-ray Photoelectron Spectroscopy (XPS) under the following conditions. XPS equipment: ULVAC-PHI, VersaProbe II Etching gun: Argon gun Acceleration voltage: 5kV Emission current: 20mA Sputtering area: 2mm x 2mm Sputtering rate: 3nm / min (SiO2 equivalent)

[0105] The content of inorganic particles in the resin layer is preferably from 10% by mass to 60% by mass, more preferably from 15% by mass to 55% by mass, and even more preferably from 20% by mass to 50% by mass, based on the total mass of the resin layer.

[0106] The content of the silica particles in the resin layer is preferably 10% by mass or more and 60% by mass or less, more preferably 15% by mass or more and 55% by mass or less, based on the total mass of the resin layer. It is more preferable that the content is from 10% by mass to 50% by mass.

[0107] The resin layer may contain conductive particles for the purpose of controlling electrostatic charge and resistance. Examples of the conductive particles include carbon black and the above-mentioned inorganic particles having electrical conductivity.

[0108] Methods for forming a resin layer on the surface of magnetic particles include, for example, a wet method and a dry method. The wet method is a method that uses a solvent to dissolve or disperse the resin that constitutes the resin layer. On the other hand, the dry method is a method that does not use the above solvent.

[0109] Examples of wet manufacturing methods include an immersion method in which magnetic particles are immersed in a resin liquid for forming a resin layer to coat them, a spray method in which a resin liquid for forming a resin layer is sprayed onto the surfaces of magnetic particles, a fluidized bed method in which magnetic particles are fluidized in a fluidized bed and then sprayed with a resin liquid for forming a resin layer, and a kneader coater method in which magnetic particles are mixed with a resin liquid for forming a resin layer in a kneader coater and the solvent is removed. These manufacturing methods may be repeated or combined. The resin liquid for forming the resin layer used in the wet manufacturing method is prepared by dissolving or dispersing the resin, inorganic particles, and other components in a solvent. The solvent is not particularly limited, and examples of the solvent that can be used include aromatic hydrocarbons such as toluene and xylene, ketones such as acetone and methyl ethyl ketone, and ethers such as tetrahydrofuran and dioxane.

[0110] An example of a dry manufacturing method is a method in which a mixture of magnetic particles and a resin for forming a resin layer is heated in a dry state to form a resin layer. Specifically, for example, the magnetic particles and the resin for forming the resin layer are mixed in a gas phase and heated and melted to form a resin layer.

[0111] The ratio B / A can be controlled by the manufacturing conditions. For example, in a manufacturing method in which the kneader-coater method is repeated multiple times (e.g., twice) to form a resin layer in stages, the mixing time of the particles to be coated and the resin liquid for forming the resin layer in the final kneader-coater process is adjusted to control the ratio B / A. The longer the mixing time in the final kneader-coater process, the smaller the ratio B / A tends to be. In another example, in a production method in which a liquid composition containing inorganic particles (which may or may not contain resin) is applied by a spray method to the surface of a resin-coated carrier produced by a kneader coater method, the particle size and content of the inorganic particles contained in the liquid composition, or the amount of the liquid composition applied to the resin-coated carrier, is adjusted to control the ratio B / A.

[0112] The exposed area ratio of the magnetic particles on the carrier surface is more preferably 5% to 30%, more preferably 7% to 25%, and even more preferably 10% to 25%. The exposed area ratio of the magnetic particles on the carrier can be controlled by the amount of resin used to form the resin layer, and the greater the amount of resin relative to the amount of magnetic particles, the smaller the exposed area ratio.

[0113] The exposed area ratio of the magnetic particles on the carrier surface is a value determined by the following method. A target carrier and magnetic particles with the resin layer removed from the target carrier are prepared. Methods for removing the resin layer from the carrier include, for example, a method of removing the resin layer by dissolving the resin component with an organic solvent, and a method of removing the resin layer by eliminating the resin component by heating at about 800°C. The carrier and magnetic particles are each used as measurement samples, and the Fe concentration (atomic%) on the sample surface is quantified by XPS, and the exposed area ratio (%) of the magnetic particles is calculated by (Fe concentration of the carrier)÷(Fe concentration of the magnetic particles)×100.

[0114] The volume average particle diameter of the carrier is preferably from 10 μm to 120 μm, more preferably from 20 μm to 100 μm, and further preferably from 30 μm to 80 μm. The volume average particle size herein means a particle size D50v that is 50% cumulative from the small diameter side in a volume-based particle size distribution.

[0115] <Image forming device, image forming method> The image forming apparatus according to the present embodiment includes an image carrier, a charging means for charging the surface of the image carrier, an electrostatic image forming means for forming an electrostatic image on the surface of the charged image carrier, a developing means for containing an electrostatic image developer and developing the electrostatic image formed on the surface of the image carrier as a toner image with the electrostatic image developer, a transfer means for transferring the toner image formed on the surface of the image carrier to the surface of a recording medium, and a fixing means for fixing the toner image transferred to the surface of the recording medium. The electrostatic image developer according to the present embodiment is used as the electrostatic image developer.

[0116] In the image forming apparatus according to this embodiment, an image forming method (the image forming method according to this embodiment) is carried out, which includes a charging step of charging the surface of an image carrier, an electrostatic image forming step of forming an electrostatic image on the surface of the charged image carrier, a developing step of developing the electrostatic image formed on the surface of the image carrier as a toner image using the electrostatic image developer according to this embodiment, a transfer step of transferring the toner image formed on the surface of the image carrier to the surface of a recording medium, and a fixing step of fixing the toner image transferred to the surface of the recording medium.

[0117] The image forming apparatus according to the present embodiment may be any of known image forming apparatuses, such as a direct transfer type apparatus in which a toner image formed on the surface of an image holder is directly transferred to a recording medium; an intermediate transfer type apparatus in which a toner image formed on the surface of an image holder is primarily transferred to the surface of an intermediate transfer body, and the toner image transferred to the surface of the intermediate transfer body is secondarily transferred to the surface of a recording medium; an apparatus equipped with a cleaning means for cleaning the surface of the image holder after the transfer of the toner image and before charging; and an apparatus equipped with a discharging means for irradiating the surface of the image holder with discharging light to discharge it after the transfer of the toner image and before charging it. When the image forming apparatus according to the present embodiment is an intermediate transfer type apparatus, the transfer means has, for example, an intermediate transfer body onto whose surface a toner image is transferred, a primary transfer means which primarily transfers the toner image formed on the surface of the image carrier onto the surface of the intermediate transfer body, and a secondary transfer means which secondarily transfers the toner image transferred onto the surface of the intermediate transfer body onto the surface of a recording medium.

[0118] In the image forming apparatus according to the present embodiment, for example, a portion including the developing means may have a cartridge structure (process cartridge) that is detachably attached to the image forming apparatus. As the process cartridge, for example, a process cartridge that contains the electrostatic charge image developer according to the present embodiment and has the developing means is preferably used.

[0119] An example of an image forming apparatus according to the present embodiment will be described below, but the present invention is not limited to this example. In the following description, the main parts shown in the drawings will be described, and the description of the rest will be omitted.

[0120] FIG. 1 is a schematic diagram showing the configuration of an image forming apparatus according to the present embodiment. The image forming apparatus shown in Fig. 1 includes first to fourth image forming units 10Y, 10M, 10C, and 10K (image forming means) of an electrophotographic type that output images of each color of yellow (Y), magenta (M), cyan (C), and black (K) based on color-separated image data. These image forming units (hereinafter sometimes simply referred to as "units") 10Y, 10M, 10C, and 10K are arranged in parallel at predetermined distances from each other in the horizontal direction. These units 10Y, 10M, 10C, and 10K may be process cartridges that are detachably attached to the image forming apparatus.

[0121] Above each of the units 10Y, 10M, 10C, and 10K, an intermediate transfer belt (one example of an intermediate transfer body) 20 is provided, which extends through each unit. The intermediate transfer belt 20 is provided wrapped around a drive roll 22 and a support roll 24, and runs in a direction from the first unit 10Y toward the fourth unit 10K. A force is applied to the support roll 24 by a spring (not shown) or the like in a direction away from the drive roll 22, and tension is applied to the intermediate transfer belt 20 wrapped around them. An intermediate transfer body cleaning device 30 is provided on the image carrier side of the intermediate transfer belt 20, facing the drive roll 22. The developing devices (an example of developing means) 4Y, 4M, 4C, and 4K of the units 10Y, 10M, 10C, and 10K are supplied with yellow, magenta, cyan, and black toners contained in toner cartridges 8Y, 8M, 8C, and 8K, respectively.

[0122] Since the first to fourth units 10Y, 10M, 10C, and 10K have the same configuration and operation, the first unit 10Y that forms a yellow image and is disposed upstream in the direction in which the intermediate transfer belt travels will be described here as a representative.

[0123] The first unit 10Y has a photoconductor 1Y that acts as an image carrier. Around the photoconductor 1Y, a charging roll (an example of a charging means) 2Y that charges the surface of the photoconductor 1Y to a predetermined potential, an exposure device (an example of an electrostatic image forming means) 3 that exposes the charged surface to a laser beam 3Y based on a color-separated image signal to form an electrostatic image, a developing device (an example of a developing means) 4Y that supplies charged toner to the electrostatic image to develop it, a primary transfer roll 5Y (an example of a primary transfer means) that transfers the developed toner image onto an intermediate transfer belt 20, and a photoconductor cleaning device (an example of a cleaning means) 6Y that removes toner remaining on the surface of the photoconductor 1Y after the primary transfer are arranged in this order. The primary transfer roll 5Y is disposed inside the intermediate transfer belt 20, and is provided at a position facing the photoconductor 1Y. A bias power supply (not shown) that applies a primary transfer bias is connected to the primary transfer rolls 5Y, 5M, 5C, and 5K of each unit. Each bias power supply changes the value of the transfer bias applied to each primary transfer roll under the control of a control unit (not shown).

[0124] Hereinafter, the operation of forming a yellow image in the first unit 10Y will be described. First, prior to operation, the surface of the photoconductor 1Y is charged to a potential of −600V to −800V by the charging roll 2Y. The photoconductor 1Y has a conductivity (for example, a volume resistivity of 1×10 at 20° C. -6The photosensitive layer is formed by laminating a photosensitive layer on a substrate having a resistivity of Ωcm or less. This photosensitive layer is usually highly resistive (the resistance of ordinary resins), but when irradiated with a laser beam, the resistivity of the portion irradiated with the laser beam changes. Therefore, the exposed surface of the charged photoreceptor 1Y is irradiated with a laser beam 3Y from the exposure device 3 in accordance with image data for yellow sent from a control unit (not shown). As a result, an electrostatic charge image of a yellow image pattern is formed on the surface of the photoreceptor 1Y.

[0125] An electrostatic image is an image formed on the surface of the photoconductor 1Y by electrostatic charging. The laser beam 3Y reduces the resistivity of the irradiated parts of the photosensitive layer, causing the charged charges on the surface of the photoconductor 1Y to flow, while the charges remain in the parts not irradiated by the laser beam 3Y. This is a so-called negative latent image. The electrostatic image formed on the photoconductor 1Y rotates to a predetermined developing position as the photoconductor 1Y travels. At this developing position, the electrostatic image on the photoconductor 1Y is developed into a toner image by the developing device 4Y and made visible.

[0126] The developing device 4Y contains an electrostatic image developer including at least yellow toner and a carrier, for example. The yellow toner is triboelectrically charged by being stirred inside the developing device 4Y, and is held on a developer roll (an example of a developer holder) with a charge of the same polarity (negative polarity) as the charge on the photoconductor 1Y. As the surface of the photoconductor 1Y passes through the developing device 4Y, the yellow toner electrostatically adheres to the discharged latent image portion on the surface of the photoconductor 1Y, and the latent image is developed with the yellow toner. The photoconductor 1Y on which the yellow toner image has been formed continues to travel at a predetermined speed, and the toner image developed on the photoconductor 1Y is transported to a predetermined primary transfer position.

[0127] When the yellow toner image on the photoreceptor 1Y is transported to the primary transfer position, a primary transfer bias is applied to the primary transfer roll 5Y, and an electrostatic force from the photoreceptor 1Y toward the primary transfer roll 5Y acts on the toner image, and the toner image on the photoreceptor 1Y is transferred onto the intermediate transfer belt 20. The transfer bias applied at this time has a polarity (+) opposite to the polarity (-) of the toner, and is controlled to, for example, +10 μA by a control unit (not shown) in the first unit 10Y. On the other hand, the toner remaining on the photoconductor 1Y is removed and collected by the photoconductor cleaning device 6Y.

[0128] The primary transfer bias applied to the primary transfer rolls 5M, 5C, and 5K subsequent to the second unit 10M is also controlled in accordance with the first unit. In this manner, the intermediate transfer belt 20 onto which the yellow toner image has been transferred by the first unit 10Y is conveyed successively through the second to fourth units 10M, 10C, and 10K, where the toner images of each color are transferred and superimposed.

[0129] The intermediate transfer belt 20 onto which the four color toner images have been transferred in multiple layers through the first to fourth units reaches a secondary transfer section that is composed of the intermediate transfer belt 20, a support roll 24 that contacts the inner surface of the intermediate transfer belt, and a secondary transfer roll (an example of a secondary transfer means) 26 arranged on the image bearing surface side of the intermediate transfer belt 20. Meanwhile, a recording paper (an example of a recording medium) P is fed at a predetermined timing into the gap between the secondary transfer roll 26 and the intermediate transfer belt 20 via a supply mechanism, and a secondary transfer bias is applied to the support roll 24. The transfer bias applied at this time has a (-) polarity that is the same as the (-) polarity of the toner, and an electrostatic force from the intermediate transfer belt 20 toward the recording paper P acts on the toner image, and the toner image on the intermediate transfer belt 20 is transferred onto the recording paper P. The secondary transfer bias at this time is determined according to the resistance detected by a resistance detection means (not shown) that detects the resistance of the secondary transfer section, and is voltage-controlled.

[0130] Thereafter, the recording paper P is sent to a pressure contact portion (nip portion) of a pair of fixing rolls in a fixing device (one example of a fixing means) 28, where the toner image is fixed onto the recording paper P, forming a fixed image.

[0131] The recording paper P onto which the toner image is transferred can be, for example, plain paper used in electrophotographic copying machines, printers, etc. In addition to the recording paper P, other examples of the recording medium include overhead projector sheets and the like. To further improve the smoothness of the image surface after fixing, it is preferable that the surface of the recording paper P is also smooth. For example, coated paper in which the surface of ordinary paper is coated with a resin or the like, art paper for printing, etc. are preferably used.

[0132] After the color image has been fixed, the recording paper P is conveyed toward the discharge section, and the series of color image forming operations is completed.

[0133] <Process cartridge> The process cartridge according to this embodiment is a process cartridge that contains the electrostatic image developer according to this embodiment, is equipped with a developing means that develops an electrostatic image formed on the surface of an image carrier using the electrostatic image developer into a toner image, and is detachably attached to an image forming apparatus.

[0134] The process cartridge according to this embodiment is not limited to the above configuration, and may be configured to include a developing means and, as necessary, at least one other means selected from an image carrier, a charging means, an electrostatic image forming means, and a transfer means.

[0135] An example of a process cartridge according to the present embodiment will be described below, but the present invention is not limited to this example. In the following description, the main parts shown in the drawings will be described, and the description of the rest will be omitted.

[0136] FIG. 2 is a schematic diagram showing the process cartridge according to the present embodiment. The process cartridge 200 shown in FIG. 2 is configured by, for example, a housing 117 having a mounting rail 116 and an opening 118 for exposure, and integrally combining and holding a photoconductor 107 (an example of an image carrier), a charging roll 108 (an example of a charging means) provided around the photoconductor 107, a developing device 111 (an example of a developing means), and a photoconductor cleaning device 113 (an example of a cleaning means), which are assembled into a cartridge. In FIG. 2, 109 indicates an exposure device (an example of an electrostatic image forming means), 112 indicates a transfer device (an example of a transfer means), 115 indicates a fixing device (an example of a fixing means), and 300 indicates a recording paper (an example of a recording medium). EXAMPLES

[0137] Hereinafter, the embodiments of the present invention will be described in detail with reference to examples, but the embodiments of the present invention are not limited to these examples. In the following description, unless otherwise specified, "parts" and "%" are by mass. Synthesis, processing, preparation, etc. were carried out at room temperature (25°C ± 3°C) unless otherwise noted.

[0138] <Toner Production> [Preparation of amorphous polyester resin dispersion (1)] Terephthalic acid: 96 parts Ethylene glycol: 37 parts Neopentyl glycol: 65 parts 1,9-nonanediol: 32 parts The above materials were charged into a flask, and the temperature was raised to 200°C over 1 hour. After confirming that the reaction system was stirred uniformly, 1.2 parts of dibutyltin oxide was added. The temperature was raised to 240°C over 6 hours while distilling off the generated water, and stirring was continued at 240°C for 4 hours to obtain amorphous polyester resin (1) (weight average molecular weight 13,000, glass transition temperature 62°C). The amorphous polyester resin (1) was transferred in a molten state to an emulsifier / disperser (Cavitron CD1010, Eurotech) at a rate of 100 g / min. Separately, a 0.37% concentration dilute ammonia water, prepared by diluting reagent ammonia water with ion-exchanged water, was placed in a tank and transferred to the emulsifier / disperser at a rate of 0.1 liters / min simultaneously with the amorphous polyester resin while being heated to 120°C in a heat exchanger. The emulsifier / disperser was operated at a rotor rotation speed of 60 Hz and a pressure of 5 kg / cm. 2 The operation was carried out under the above conditions to obtain an amorphous polyester resin dispersion (1) having a volume average particle size of 160 nm and a solid content of 20%.

[0139] [Preparation of crystalline polyester resin dispersion (1)] Dimethyl sebacate: 97 parts Sodium dimethyl isophthalate-5-sulfonate: 3 parts Ethylene glycol: 100 parts Dibutyltin oxide (catalyst): 0.3 parts The above materials were placed in a heated and dried three-necked flask, the air in the flask was replaced with nitrogen gas to create an inert atmosphere, and the mixture was stirred and refluxed for 5 hours at 180°C using mechanical stirring. The temperature was then gradually increased to 240°C under reduced pressure and the mixture was stirred for 2 hours. When the mixture became viscous, it was air-cooled to stop the reaction, and a crystalline polyester resin (1) (weight average molecular weight 9700, melting temperature 84°C) was obtained. 90 parts of crystalline polyester resin (1), 1.8 parts of anionic surfactant (Daiichi Kogyo Seiyaku Co., Ltd., Neogen RK), and 210 parts of ion-exchanged water were mixed, heated to 100°C, and dispersed using a homogenizer (IKA Ultra Turrax T50), and then dispersed for 1 hour using a pressure discharge Gaulin homogenizer to obtain a resin particle dispersion in which resin particles with a volume average particle size of 180 nm were dispersed. Ion-exchanged water was added to this resin particle dispersion to adjust the solid content to 20%, and a crystalline polyester resin dispersion (1) was obtained.

[0140] [Preparation of colorant dispersion (C1)] Cyan pigment (Pigment Blue 15:3, Dainichi Seika Color & Chemicals): 50 parts Anionic surfactant (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., Neogen RK): 5 parts Ion-exchanged water: 195 parts The above materials were mixed and dispersed for 60 minutes using a high-pressure impact disperser (Ultimaizer HJP30006, Sugino Machine Co., Ltd.) to obtain a colorant dispersion (C1) with a solid content of 20%.

[0141] [Preparation of release agent dispersion (W1)] Paraffin wax (HNP-9, made by Nippon Seiro Co., Ltd., melting point 75°C): 100 parts Anionic surfactant (Daiichi Kogyo Seiyaku Co., Ltd., Neogen RK): 1 part Ion-exchanged water: 350 parts The above materials were mixed and heated to 100°C, dispersed using a homogenizer (IKA Ultra Turrax T50), and then dispersed using a pressure discharge Gaulin homogenizer to obtain a release agent dispersion in which release agent particles with a volume average particle size of 200 nm were dispersed. Ion-exchanged water was added to this release agent dispersion to adjust the solid content to 20%, and this was used as release agent dispersion (W1).

[0142] [Preparation of cyan toner particles (1)] Ion-exchanged water: 200 parts Amorphous polyester resin dispersion (1): 150 parts Crystalline polyester resin dispersion (1): 20 parts Release agent dispersion (W1): 10 parts Colorant dispersion (C1): 15 parts Anionic surfactant (TaycaPower): 2.8 parts The above materials were placed in a round stainless steel flask, and 0.1N nitric acid was added to adjust the pH to 3.5, after which an aqueous solution of polyaluminum chloride (Oji Paper Co., Ltd., 30% powder product) was dissolved in 30 parts of ion-exchanged water and added. The mixture was dispersed at 30°C using a homogenizer (IKA Ultra Turrax T50), and then heated to 45°C in a heating oil bath and maintained until the volume average particle size reached 4.9 μm. Next, 60 parts of the amorphous polyester resin dispersion (1) was added and held for 30 minutes. Next, when the volume average particle size became 5.2 μm, 60 parts of the amorphous polyester resin dispersion (1) was further added and held for 30 minutes. Next, 20 parts of a 10% NTA (nitrilotriacetic acid) metal salt aqueous solution (Chilest 70, manufactured by Chelesto Corporation) was added, and a 1N aqueous sodium hydroxide solution was added to adjust the pH to 8.8. Next, 1 part of an anionic surfactant (TaycaPower) was added, and the mixture was heated to 96°C while continuing to stir, and maintained at that temperature for 6 hours. Next, the mixture was cooled to 20°C at a rate of 20°C / min. Next, the mixture was filtered, thoroughly washed with ion-exchanged water, and dried to obtain cyan toner particles (1) having a volume average particle size of 5.7 μm.

[0143] [Preparation of cyan toner particles (2) to (11)] Cyan toner particles (2) to (11) were prepared in the same manner as in the preparation of cyan toner particles (1), except that the pH and temperature in the fusion / coalescence step or the amount of crystalline polyester resin dispersion (1) used were changed as shown in Table 1.

[0144] [Preparation of Cyan Toners (1) to (11)] 100 parts of any of the cyan toner particles (1) to (11) and 1.5 parts of hydrophobic silica particles (RY50, manufactured by Nippon Aerosil Co., Ltd.) were placed in a sample mill and mixed for 30 seconds at a rotation speed of 10,000 rpm. The mixture was then sieved through a vibrating sieve with 45 μm openings to obtain cyan toners (1) to (11), respectively.

[0145] [Table 1]

[0146] <Preparation of ferrite particles> 1318 parts of Fe2O3, 587 parts of Mn(OH)2, and 96 parts of Mg(OH)2 were mixed and pre-fired at 900°C for 4 hours. The pre-fired product, 6.6 parts of polyvinyl alcohol, 0.5 parts of polycarboxylic acid as a dispersant, and zirconia beads with a media diameter of 1 mm were added to water, and the mixture was ground and mixed in a sand mill to obtain a dispersion. The volume average particle size of the particles in the dispersion was 1.5 μm. The dispersion liquid was used as a raw material, and granulated and dried using a spray dryer to obtain granules with a volume average particle size of 37 μm. Next, in an oxygen-nitrogen mixed atmosphere with an oxygen partial pressure of 1%, main sintering was performed using an electric furnace at a temperature of 1450°C for 4 hours, and then heating was performed in the air at a temperature of 900°C for 3 hours to obtain sintered particles. The sintered particles were crushed and classified to obtain ferrite particles (1) with a volume average particle size of 35 μm. The arithmetic mean height Ra (JIS B0601:2001) of the roughness curve of the ferrite particles (1) was 0.6 μm.

[0147] <Preparation of silica particles to be added to carrier resin layer> [Silica particles (1)] Commercially available hydrophilic silica particles (fumed silica particles, no surface treatment, volume average particle size 40 nm) were prepared and designated as silica particles (1).

[0148] [Silica particles (2)] 890 parts of methanol and 210 parts of 9.8% aqueous ammonia were added and mixed in a 1.5 L glass reaction vessel equipped with a stirrer, a dropping nozzle, and a thermometer to obtain an alkaline catalyst solution. After adjusting the alkaline catalyst solution to 45°C, 550 parts of tetramethoxysilane and 140 parts of 7.6% aqueous ammonia were dropped simultaneously over a period of 450 minutes while stirring to obtain a silica particle dispersion (A). The silica particles in the silica particle dispersion (A) have a volume average particle size of 4 nm, a volume particle size distribution index (the square root of the ratio of the particle size D16v at 16% cumulative from the small diameter side in the volume-based particle size distribution to the particle size D84v at 84% cumulative (D84v / D16v) 1 / 2 )1.2. 300 parts of the silica particle dispersion (A) were put into an autoclave equipped with a stirrer, and the stirrer was rotated at a rotation speed of 100 rpm. While continuing to rotate the stirrer, liquefied carbon dioxide was injected into the autoclave from a carbon dioxide cylinder via a pump, and the inside of the autoclave was heated with a heater while the inside of the autoclave was pressurized with a pump, so that the inside of the autoclave was in a supercritical state of 150°C and 15 MPa. The pressure valve was operated to keep the inside of the autoclave at 15 MPa, and supercritical carbon dioxide was circulated to remove methanol and water from the silica particle dispersion (A). When the amount of carbon dioxide supplied to the autoclave reached 900 parts, the supply of carbon dioxide was stopped, and a powder of silica particles was obtained. The inside of the autoclave was kept at 150°C and 15 MPa by a heater and a pump to maintain the supercritical state of carbon dioxide, and while continuing to rotate the stirrer of the autoclave, 50 parts of hexamethyldisilazane per 100 parts of silica particles was injected into the autoclave by an entrainer pump, and the temperature inside the autoclave was raised to 180°C and reacted for 20 minutes. Next, supercritical carbon dioxide was again circulated in the autoclave to remove excess hexamethyldisilazane. Next, the stirring was stopped, the pressure valve was opened to release the pressure inside the autoclave to atmospheric pressure, and the temperature was lowered to room temperature (25°C). Thus, silica particles (2) surface-treated with hexamethyldisilazane were obtained. The silica particles (2) had a volume average particle size of 4 nm.

[0149] [Silica particles (3)] The silica particles (2) were prepared in the same manner, except that the amount of tetramethoxysilane and 7.6% aqueous ammonia added when preparing the silica particle dispersion (A) was increased to change the volume average particle size of the silica particles in the silica particle dispersion to 6 nm, and silica particles (3) surface-treated with hexamethyldisilazane were obtained. The silica particles (3) had a volume average particle size of 7 nm.

[0150] [Silica particles (4)] Commercially available hydrophobic silica particles (fumed silica particles surface-treated with hexamethyldisilazane, volume average particle size 12 nm) were prepared and designated as silica particles (4).

[0151] [Silica particles (5)] Commercially available hydrophilic silica particles (fumed silica particles, no surface treatment, volume average particle size 62 nm) were prepared and designated as silica particles (5).

[0152] [Silica particles (6)] Commercially available hydrophobic silica particles (fumed silica particles surface-treated with hexamethyldisilazane, volume average particle size 88 nm) were prepared and designated as silica particles (6).

[0153] [Silica particles (7)] Commercially available hydrophobic silica particles (fumed silica particles surface-treated with hexamethyldisilazane, volume average particle size 93 nm) were prepared and designated as silica particles (7).

[0154] [Inorganic particles (8)] Commercially available calcium carbonate particles (volume average particle size: 20 nm) were prepared and used as inorganic particles (8).

[0155] [Inorganic particles (9)] Commercially available barium carbonate particles (volume average particle size: 40 nm) were prepared and used as inorganic particles (9).

[0156] [Inorganic particles (10)] Commercially available barium sulfate particles (BARIFINE BF-40, volume average particle size 10 nm) were prepared and used as inorganic particles (10).

[0157] [Inorganic particles (11)] Commercially available barium sulfate particles (BARIFINE BF-20, volume average particle size 30 nm) were prepared and used as inorganic particles (11).

[0158] [Inorganic particles (12)] Commercially available barium sulfate particles (BARIFINE BF-21, volume average particle size 50 nm) were prepared and used as inorganic particles (12).

[0159] [Inorganic particles (13)] Commercially available barium sulfate particles (BARIFINE BF-10, volume average particle size 60 nm) were prepared and used as inorganic particles (13).

[0160] <Preparation of Coating Agent for Forming Carrier Resin Layer> [Coating agent (1)] Cyclohexyl methacrylate resin (weight average molecular weight 350,000): 6.6 parts Perfluoropropylethyl methacrylate-methyl methacrylate copolymer (polymerization ratio by mass: 30:70, weight average molecular weight: 19,000): 9.9 parts Carbon black (Cabot, VXC72): 0.5 parts Silica particles (1): 20 parts Toluene: 250 parts Isopropyl alcohol: 50 parts The above materials and glass beads (diameter 1 mm, same amount as toluene) were put into a sand mill and stirred at a rotation speed of 190 rpm for 30 minutes to obtain coating agent (1) with a solid content of 11%. The weight average molecular weight of the resin constituting coating agent (1) is 150,000.

[0161] [Coating agents (2)~(7)] Coating agents (2) to (7) were obtained in the same manner as in the preparation of coating agent (1), except that the silica particles (1) were changed to any of silica particles (2) to (7), respectively.

[0162] [Coating agents (8)~(11)] Coating agents (8) to (11) were obtained in the same manner as in the preparation of coating agent (1), except that the amount of silica particles (1) added was changed as follows. Coating agent (8): 10 parts of silica particles (1) Coating agent (9): 12 parts of silica particles (1) Coating agent (10): 30 parts of silica particles (1) Coating agent (11): 40 parts of silica particles (1)

[0163] [Coating agent (12-1)] Cyclohexyl methacrylate resin (weight average molecular weight 50,000): 20 parts Polyisocyanate (Tosoh Corporation, Coronate L): 4 parts Carbon black (Cabot, VXC72): 1 part Toluene: 425 parts Methanol: 50 parts The above materials and glass beads (diameter 1 mm, same amount as toluene) were placed in a sand mill and stirred at a rotation speed of 1200 rpm for 30 minutes to obtain a coating agent (12-1) with a solid content of 5%.

[0164] [Coating agent (12-2)] Silica particles (4): 8 parts Toluene: 92 parts The above materials and glass beads (diameter 1 mm, same amount as toluene) were placed in a sand mill and stirred at a rotation speed of 1200 rpm for 30 minutes to obtain a coating agent (12-2) with a solid content of 8%.

[0165] [Coating agent (13)] Cyclohexyl methacrylate resin (weight average molecular weight 350,000): 3.3 parts Perfluoropropylethyl methacrylate-methyl methacrylate copolymer (polymerization ratio by mass: 30:70, weight average molecular weight: 19,000): 13.2 parts Carbon black (Cabot, VXC72): 0.5 parts Silica particles (1): 20 parts Toluene: 250 parts Isopropyl alcohol: 50 parts The above materials and glass beads (diameter 1 mm, same amount as toluene) were put into a sand mill and stirred at a rotation speed of 190 rpm for 30 minutes to obtain a coating agent (13) with a solid content of 11%. The weight average molecular weight of the resin constituting the coating agent (13) is 85,000.

[0166] [Coating agent (14)] Cyclohexyl methacrylate resin (weight average molecular weight 350,000): 9.9 parts Perfluoropropylethyl methacrylate-methyl methacrylate copolymer (polymerization ratio by mass: 30:70, weight average molecular weight: 19000): 6.6 parts Carbon black (Cabot, VXC72): 0.5 parts Silica particles (1): 20 parts Toluene: 250 parts Isopropyl alcohol: 50 parts The above materials and glass beads (diameter 1 mm, same amount as toluene) were put into a sand mill and stirred at a rotation speed of 190 rpm for 30 minutes to obtain a coating agent (14) with a solid content of 11%. The weight average molecular weight of the resin constituting the coating agent (14) is 210,000.

[0167] [Coating agent (15)] Cyclohexyl methacrylate resin (weight average molecular weight 350,000): 16.5 parts Carbon black (Cabot, VXC72): 0.5 parts Silica particles (1): 20 parts Toluene: 250 parts Isopropyl alcohol: 50 parts The above materials and glass beads (diameter 1 mm, same amount as toluene) were placed in a sand mill and stirred at a rotation speed of 190 rpm for 30 minutes to obtain a coating agent (15) with a solid content of 11%.

[0168] [Coating agent (16)] Cyclohexyl methacrylate resin (weight average molecular weight 350,000): 6.6 parts Perfluoropropylethyl methacrylate-methyl methacrylate copolymer (polymerization ratio by mass: 30:70, weight average molecular weight: 19,000): 9.9 parts Carbon black (Cabot, VXC72): 0.5 parts ·Inorganic particles (8): 20 parts Toluene: 250 parts Isopropyl alcohol: 50 parts The above materials and glass beads (diameter 1 mm, same amount as toluene) were placed in a sand mill and stirred at a rotation speed of 190 rpm for 30 minutes to obtain a coating agent (16) with a solid content of 11%.

[0169] [Coating agent (17)] Cyclohexyl methacrylate resin (weight average molecular weight 350,000): 6.6 parts Perfluoropropylethyl methacrylate-methyl methacrylate copolymer (polymerization ratio by mass: 30:70, weight average molecular weight: 19,000): 9.9 parts Carbon black (Cabot, VXC72): 0.5 parts ·Inorganic particles (9): 20 parts Toluene: 250 parts Isopropyl alcohol: 50 parts The above materials and glass beads (diameter 1 mm, same amount as toluene) were placed in a sand mill and stirred at a rotation speed of 190 rpm for 30 minutes to obtain a coating agent (17) with a solid content of 11%.

[0170] [Coating agent (18)] Cyclohexyl methacrylate resin (weight average molecular weight 350,000): 6.6 parts Perfluoropropylethyl methacrylate-methyl methacrylate copolymer (polymerization ratio by mass: 30:70, weight average molecular weight: 19,000): 9.9 parts Carbon black (Cabot, VXC72): 0.5 parts ·Inorganic particles (10): 20 parts Toluene: 250 parts Isopropyl alcohol: 50 parts The above materials and glass beads (diameter 1 mm, same amount as toluene) were placed in a sand mill and stirred at a rotation speed of 190 rpm for 30 minutes to obtain a coating agent (18) with a solid content of 11%.

[0171] [Coating agent (19)] Cyclohexyl methacrylate resin (weight average molecular weight 350,000): 6.6 parts Perfluoropropylethyl methacrylate-methyl methacrylate copolymer (polymerization ratio by mass: 30:70, weight average molecular weight: 19,000): 9.9 parts Carbon black (Cabot, VXC72): 0.5 parts ·Inorganic particles (11): 20 parts Toluene: 250 parts Isopropyl alcohol: 50 parts The above materials and glass beads (diameter 1 mm, same amount as toluene) were placed in a sand mill and stirred at a rotation speed of 190 rpm for 30 minutes to obtain a coating agent (19) with a solid content of 11%.

[0172] [Coating agent (20)] Cyclohexyl methacrylate resin (weight average molecular weight 350,000): 6.6 parts Perfluoropropylethyl methacrylate-methyl methacrylate copolymer (polymerization ratio by mass: 30:70, weight average molecular weight: 19,000): 9.9 parts Carbon black (Cabot, VXC72): 0.5 parts ·Inorganic particles (12): 20 parts Toluene: 250 parts Isopropyl alcohol: 50 parts The above materials and glass beads (diameter 1 mm, same amount as toluene) were placed in a sand mill and stirred at a rotation speed of 190 rpm for 30 minutes to obtain a coating agent (20) with a solid content of 11%.

[0173] [Coating agent (21)] Cyclohexyl methacrylate resin (weight average molecular weight 350,000): 6.6 parts Perfluoropropylethyl methacrylate-methyl methacrylate copolymer (polymerization ratio by mass: 30:70, weight average molecular weight: 19,000): 9.9 parts Carbon black (Cabot, VXC72): 0.5 parts ·Inorganic particles (13): 20 parts Toluene: 250 parts Isopropyl alcohol: 50 parts The above materials and glass beads (diameter 1 mm, same amount as toluene) were placed in a sand mill and stirred at a rotation speed of 190 rpm for 30 minutes to obtain a coating agent (21) with a solid content of 11%.

[0174] <Preparation of Resin-Coated Carrier> [Career (1)] 1000 parts of the ferrite particles (1) and 125 parts of the coating agent (1) were put into a kneader and mixed at room temperature (25° C.) for 20 minutes, then heated to 70° C. and dried under reduced pressure. The dried product was cooled to room temperature (25° C.), and 125 parts of the coating agent (1) was added and mixed at room temperature (25° C.) for 20 minutes. Then, the mixture was heated to 70° C. and dried under reduced pressure. Next, the dried product was taken out of the kneader and sieved through a mesh with 75 μm openings to remove coarse powder, thereby obtaining a carrier (1).

[0175] [Career (2)~(7)] Carriers (2) to (7) were prepared in the same manner as carrier (1), except that the mixing time after the additional addition of coating agent (1) was changed as shown in Table 3, to obtain carriers (2) to (7).

[0176] [Career (8)~(13)] Carriers (8) to (13) were obtained in the same manner as in the preparation of carrier (1), except that the coating agent (1) was changed to any of the coating agents (2) to (7), respectively.

[0177] [Career (14)~(19)] Carriers (14) to (19) were obtained in the same manner as in the preparation of carrier (1), except that the amount of coating agent (1) added was changed as shown in Table 3.

[0178] [Career (20)~(23)] Carriers (20) to (23) were obtained in the same manner as in the preparation of carrier (1), except that the coating agent (1) was changed to any of coating agents (8) to (11), respectively.

[0179] [Career (24)] 100 parts of ferrite particles (1) and 40 parts of coating agent (12-1) were placed in a vacuum degassing kneader, and the mixture was heated and decompressed while stirring, and then stirred and dried for 30 minutes in an atmosphere of 90°C / -720mHg. 10 parts of coating agent (12-2) were applied to the removed carrier by a spray method, and after drying, the carrier was left to stand at 150°C for 1 hour in an electric furnace for firing. The carrier was sieved through a mesh with 75μm openings to remove coarse powder, and a carrier (24) was obtained.

[0180] [Career (25)~(33)] Carriers (25) to (33) were obtained in the same manner as in the preparation of carrier (1), except that the coating agent (1) was changed to any of the coating agents (13) to (21), respectively.

[0181] <Preparation of developer> As shown in Tables 2 and 3, any one of the cyan toners (1) to (11) and any one of the carriers (1) to (33) were combined and placed in a V blender in a mixing ratio of toner:carrier = 10:100 (mass ratio), and stirred for 20 minutes to obtain cyan developers.

[0182] <Surface property index value of toner particles> The measured specific surface area of ​​the toner particles was determined from the amount of nitrogen adsorption by the BET one-point method (equilibrium relative pressure 0.3). The toner particles were taken into a flow type particle image analyzer (Sysmex FPIA-3000), the toner particles were imaged, and the two-dimensional image was processed to calculate the equivalent circle diameter from the projected area. The sum of the surface area and the sum of the volume were calculated from the equivalent circle diameters of 4,500 toner particles. The density of the toner particles was measured by measuring the true density using a Gay-Lussac type pycnometer in accordance with 8.2.2 of JIS K0061:2001.

[0183] <Measurement of dynamic viscoelasticity of toner> Using a press molding machine, 0.25 g of toner was tableted into a disk with a diameter of 8 mm and a thickness of 4 mm in an environment of 25°C ± 3°C. This disk-shaped sample was placed on the parallel plate of a rheometer (TA Instruments "ARES"). The sample was attached to the parallel plate at a temperature of 130°C, cooled to a temperature of 30°C at a rate of 1°C / min, and held at a temperature of 30°C for 30 minutes, and then measured at a temperature of 30°C. The measurement conditions were frequency: 1 Hz, angular frequency: 6.28 rad / sec, and strain: 0.03 to 20% (automatic control).

[0184] <Carrier surface analysis> The device used for three-dimensionally analyzing the carrier surface was an electron beam three-dimensional roughness analyzer ERA-8900FE manufactured by Elionix Co., Ltd. The carrier surface analysis using the ERA-8900FE was specifically carried out as follows. The surface of one carrier particle was magnified 5000 times, and 300 measurement points were taken along the long side and short side, respectively, to perform 3D measurements, obtaining 3D image data for an area of ​​24μm x 18μm. For the 3D image data, the limit wavelength of the spline filter was set to 12μm to remove wavelengths with a period of 12μm or more, and further, the cutoff value of the Gaussian high-pass filter was set to 2.0μm to remove wavelengths with a period of 2.0μm or more, obtaining 3D roughness curve data. From the 3D roughness curve data, the central 12μm x 12μm area (plan view area A = 144μm) 2 ) surface area B (μm 2 ) was calculated to determine the ratio B / A. The ratio B / A was calculated for each of 100 carriers, and the arithmetic average was calculated.

[0185] <Measurement of the average particle size of silica particles in the resin layer> The carrier was embedded in epoxy resin and cut with a microtome to prepare a carrier cross section. SEM images of the carrier cross section taken with a scanning transmission electron microscope (Hitachi, Ltd., S-4100) were imported into an image processing analyzer (Nireco, Ltd., Luzex AP) and image analysis was performed. 100 silica particles (primary particles) were randomly selected from the resin layer, and the circle equivalent diameter (nm) of each was calculated and the arithmetic average was calculated to obtain the average particle diameter (nm) of the silica particles.

[0186] <Measurement of the average thickness of the resin layer> The SEM image was imported into an image processing analyzer (Nireco Corporation, Luzex AP) and image analysis was performed. The thickness (μm) of the resin layer was measured at 10 randomly selected points per carrier particle, and then measurements were taken for 100 carrier particles, and the arithmetic average of all measurements was calculated to determine the average thickness (μm) of the resin layer.

[0187] <Measurement of silicon element concentration> The carrier was used as a sample and analyzed by X-ray photoelectron spectroscopy (XPS) under the following conditions, and the silicon element concentration (atomic %) was calculated from the peak intensity of each element. XPS equipment: ULVAC-PHI, VersaProbe II Etching gun: Argon gun Acceleration voltage: 5kV Emission current: 20mA Sputtering area: 2mm x 2mm Sputtering rate: 3nm / min (SiO2 equivalent)

[0188] <Evaluation of fogging> A modified image forming apparatus DocuPrintColor3540 (manufactured by Fuji Xerox Co., Ltd.) was prepared, and a developer was placed in the developing device. The toner cartridge was filled with the same type of toner as that used to prepare the developer (for example, when the developer in the developing device was a combination of cyan toner (1) and carrier (1), cyan toner (1) was placed in the toner cartridge). The image forming apparatus was left in an environment with a temperature of 25°C and a relative humidity of 55% for 24 hours. Under the environment of a temperature of 25°C and a relative humidity of 55%, 50,000 test images with a cyan image density of 5% were printed on A3 size paper. Next, 10 test images with a cyan image density of 40% were printed on the entire surface of A3 size paper, and the presence or absence of fog was observed with the naked eye and with a 5x magnification loupe, and classified as follows.

[0189] A: Overlapping of all 10 sheets is not permitted. B: A slight amount of fogging can be seen on one sheet with a magnifying glass, but it is not enough to cause problems. C: Slight fogging was observed on several sheets with a magnifying glass, but it was so slight that it did not interfere with practical use. D: Fog is visible to the naked eye on multiple sheets, but is so slight that it does not interfere with practical use. E: Fog was observed with the naked eye on all 10 sheets, and they were unsuitable for practical use.

[0190] [Table 2]

[0191] [Table 3] [Explanation of symbols]

[0192] 1Y, 1M, 1C, 1K Photoconductor (an example of an image carrier) 2Y, 2M, 2C, 2K Charging roll (an example of a charging means) 3 Exposure device (an example of an electrostatic image forming means) 3Y, 3M, 3C, 3K laser beam 4Y, 4M, 4C, 4K developing device (an example of developing means) 5Y, 5M, 5C, 5K Primary transfer roll (an example of a primary transfer means) 6Y, 6M, 6C, 6K Photoconductor cleaning device (an example of a cleaning means) 8Y, 8M, 8C, 8K toner cartridges 10Y, 10M, 10C, 10K Image forming units 20 Intermediate transfer belt (an example of an intermediate transfer body) 22 Driving Roll 24 Support roll 26 Secondary transfer roll (an example of a secondary transfer means) 28 Fixing device (an example of a fixing means) 30 Intermediate transfer body cleaning device P Recording paper (an example of a recording medium) 107 Photoconductor (an example of an image carrier) 108 Charging roll (an example of charging means) 109 Exposure device (an example of electrostatic image forming means) 111 Developing device (an example of developing means) 112 Transfer device (an example of a transfer means) 113 Photoconductor cleaning device (an example of a cleaning means) 115 Fixing device (an example of fixing means) 116 Mounting Rail 117 Cabinet 118 Exposure Aperture 200 Process Cartridge 300 Recording paper (an example of a recording medium)

Claims

1. a toner comprising toner particles and an external additive, the toner particles having a surface property index value of 1.0 or more and less than 2.0; a carrier having magnetic particles and a resin layer covering the magnetic particles, the weight average molecular weight of the resin in the resin layer being 85,000 or more and 210,000 or less, the resin layer containing carbon black and inorganic particles other than carbon black, and a ratio B / A of a plan view area A to a surface area B being 1.020 or more and 1.100 or less when the surface is three-dimensionally analyzed; 1. An electrostatic image developer comprising:

2. 2. The electrostatic image developer according to claim 1, wherein the surface index value is 1.2 or more and 1.8 or less.

3. 3. The electrostatic image developer according to claim 1, wherein the ratio B / A is 1.040 or more and 1.080 or less.

4. The electrostatic image developer according to claim 1, wherein the inorganic particles have an average particle size of 5 nm or more and 90 nm or less.

5. 5. The electrostatic image developer according to claim 4, wherein the inorganic particles have an average particle size of 5 nm or more and 70 nm or less.

6. 6. The electrostatic image developer according to claim 1, wherein the resin layer has an average thickness of 0.6 μm or more and 1.4 μm or less.

7. 7. The electrostatic image developer according to claim 6, wherein the average thickness of the resin layer is from 0.8 [mu]m to 1.2 [mu]m.

8. The toner has a storage modulus G′ of 6.0×10 at a temperature of 30° C. in dynamic viscoelasticity measurement. 8 Pa or more 1.5×10 9 The electrostatic image developer according to any one of claims 1 to 7, wherein the viscosity of the electrostatic image developer is 1 Pa or less.

9. The storage elastic modulus G' is 8.0×10 8 Pa or more 1.2×10 9 9. The electrostatic image developer according to claim 8, wherein the viscosity is 0.1 Pa or less.

10. the inorganic particles include silica particles, 10. The electrostatic image developer according to claim 1, wherein the silicon element concentration on the surface of the carrier determined by X-ray photoelectron spectroscopy is more than 2 atomic % and less than 20 atomic %.

11. The electrostatic image developer according to claim 1, wherein the resin layer contains an acrylic resin containing cyclohexyl (meth)acrylate as a polymerization component.

12. a developing unit that contains the electrostatic image developer according to any one of claims 1 to 11 and develops an electrostatic image formed on a surface of an image carrier into a toner image by the electrostatic image developer, A process cartridge that is detachably attached to an image forming apparatus.

13. An image carrier; a charging means for charging the surface of the image carrier; an electrostatic image forming means for forming an electrostatic image on the charged surface of the image carrier; a developing unit that contains the electrostatic image developer according to any one of claims 1 to 11 and develops the electrostatic image formed on the surface of the image carrier into a toner image by the electrostatic image developer; a transfer means for transferring the toner image formed on the surface of the image carrier to a surface of a recording medium; a fixing means for fixing the toner image transferred onto the surface of the recording medium; An image forming apparatus comprising:

14. a charging step of charging the surface of the image carrier; an electrostatic image forming step of forming an electrostatic image on the charged surface of the image carrier; a developing step of developing the electrostatic image formed on the surface of the image carrier into a toner image by using the electrostatic image developer according to any one of claims 1 to 11; a transfer step of transferring the toner image formed on the surface of the image carrier onto a surface of a recording medium; a fixing step of fixing the toner image transferred onto the surface of the recording medium; The image forming method according to claim 1,

Citation Information

Patent Citations

  • Toner for electrostatic charge image development, and method for manufacturing the toner

    JP2006301618A

  • Developer for electrostatic image development

    JP2008304745A

  • Carrier for developer for developing electrostatic charge image, developer for developing the electrostatic charge image, toner cartridge, process cartridge, and image forming apparatus

    JP2011186005A

  • Carrier and developer

    JP2016212254A

  • Toner for electrostatic charge image development, electrostatic charge image developer, toner cartridge, process cartridge, image forming apparatus, and image forming method

    JP2019168533A